Granulated body, resin composition and production method and use of them
Patent Information
- Application Number
- JP2023136446
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-08-24
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2043-08-24
AI Technical Summary
【0034】 本開示では、取り扱い性、混練機への供給性に優れ、かつ樹脂やゴム中における植物由来の繊維状フィラーの分散性に優れた造粒体を提供できる。
Smart Images

Figure 2025030815000001 
Figure 2025030815000002 
Figure 2025030815000003
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a granule and a resin composition containing a plant-derived filler, as well as a method for producing the same and uses thereof. [Background technology]
[0002] Cellulose, a fiber derived from plants, has a small environmental impact, is a sustainable resource, and has excellent properties such as high elastic modulus, high strength, and low linear expansion coefficient. Therefore, it is used in a wide range of applications, such as materials for paper, films, sheets, and resin composite materials (for example, resin reinforcing agents). In rubber compositions, cellulose is also added as a reinforcing agent to improve the mechanical properties of rubber. Therefore, various methods have been proposed for uniformly dispersing cellulose in resins and rubbers.
[0003] Japanese Patent Laid-Open Publication No. 2019-178266 (Patent Document 1) discloses a composite to be blended with a resin, which is composed of cellulose and a coating layer that covers at least a part of the surface of the cellulose and contains a fluorene compound having multiple hydroxyl groups. In this document, a resin composition is produced by melt-kneading a wet composite containing cellulose nanofibers and a fluorene compound with polypropylene.
[0004] Japanese Patent Application Laid-Open No. 2020-128475 (Patent Document 2) discloses a hybrid filler for mixing with resins, which contains a composite of cellulose fibers and fine particles. As the fine particles, inorganic particles such as silica, triiron tetroxide, and graphene are described.
[0005] JP 2022-001631 A (Patent Document 3) discloses a method for producing a dry powder of cellulose fiber to be mixed with a resin, the method including a slurry preparation step of preparing a slurry containing cellulose fiber and water, and a granulation step of stirring the slurry under reduced pressure to form a dry powder of the cellulose fiber, in which the cellulose fiber particles formed by the stirring in the granulation step are chopper-pulverized.
[0006] Japanese Patent Laid-Open No. 2022-169489 (Patent Document 4) and Japanese Patent Laid-Open No. 2022-169490 (Patent Document 5) disclose a method for producing a dried body to be mixed with a thermoplastic resin, the method including a drying and granulation step of removing the liquid from a dispersion containing fine cellulose fibers, a dispersant, and a liquid to obtain a dried body.
[0007] JP 2022-184494 A (Patent Document 6) discloses a method for producing a cellulose fiber composite resin raw material used in the production of a cellulose fiber composite resin molding, in which undefibrated hydrophobically modified cellulose, a solvent, and a particulate thermoplastic resin are shear-mixed to defibrate the cellulose and compound it with the particulate thermoplastic resin to obtain a cellulose fiber composite resin raw material. [Prior art documents] [Patent documents]
[0008] [Patent Document 1] JP 2019-178266 A [Patent Document 2] JP 2020-128475 A [Patent Document 3] JP 2022-001631 A [Patent Document 4] JP 2022-169489 A [Patent Document 5] JP 2022-169490 A [Patent Document 6] JP 2022-184494 A Summary of the Invention [Problem to be solved by the invention]
[0009] However, even if the composites of Patent Documents 1 and 2 are blended with a resin or rubber, it is difficult to uniformly disperse cellulose in the resin or rubber. Moreover, even if a thermoplastic resin composition is prepared by the manufacturing methods of Patent Documents 3 to 6, the handling property for uniformly dispersing cellulose is low, and it is difficult to prepare a composition in which cellulose is highly dispersed in the thermoplastic resin.
[0010] Therefore, an object of the present invention is to provide a granule and a resin composition which are excellent in handleability and feedability to a kneader, and which exhibit excellent dispersibility of a plant-derived fibrous filler in a resin or rubber, as well as production methods and uses thereof. [Means for solving the problem]
[0011] As a result of intensive research into achieving the above object, the present inventors have combined a plant-derived fibrous filler (A) having an average fiber diameter of 0.5 to 100 μm with an organic material (B) which is solid at room temperature and normal pressure and has a molecular weight of 100 to 1000, and have developed a composite material having a bulk density of 0.1 to 0.5 g / cm. 3 The present inventors have found that by adjusting the composition ratio to the above range, it is possible to provide granules which are excellent in handleability and feedability to a kneader, and which exhibit excellent dispersibility of the plant-derived filler in resin or rubber, and have completed the present invention.
[0012] That is, the granule as embodiment [1] of the present disclosure (or the present invention) is A composite material containing a fibrous filler (A) derived from a plant and an organic material (B) and having a bulk density of 0.1 to 0.5 g / cm 3 A granule comprising: The average fiber diameter of the fibrous filler (A) is 0.5 to 100 μm, The organic material (B) is solid at room temperature and normal pressure, and The organic material (B) has a molecular weight of 100-1,000.
[0013] An embodiment [2] of the present disclosure is an embodiment in which, in the embodiment [1], the proportion of the organic material (B) is 1 to 70 parts by mass per 100 parts by mass of the fibrous filler (A).
[0014] The embodiment [3] of the present disclosure is an embodiment in which the granules of the embodiment [1] or [2] are used for kneading with a resin or rubber.
[0015] An embodiment [4] of the present disclosure is any one of the embodiments [1] to [3] above, wherein the organic material (B) is a non-fibrous organic material having a melting point of 100° C. or higher.
[0016] An embodiment [5] of the present disclosure is any one of the embodiments [1] to [4], in which the organic material (B) is a compound having a hydrophobic skeleton and a polar group.
[0017] An embodiment [6] of the present disclosure is an embodiment in which, in the embodiment [5], the hydrophobic skeleton is a polycyclic aromatic ring.
[0018] An embodiment [7] of the present disclosure is any one of the embodiments [1] to [6], in which the organic material (B) is a compound represented by the following formula (1):
[0019] [ka]
[0020] (Wherein, ring Z is an arene ring, R 1 and R 2 is a substituent, X 1 represents a heteroatom-containing functional group, k represents an integer of 0 to 4, n represents an integer of 1 or more, and p represents an integer of 0 or more.
[0021] The embodiment [8] of the present disclosure relates to the above-mentioned embodiment [7], wherein in the formula (1), X 1 But, the base -(OA) m1 In this embodiment, the group is --OH (wherein A is an alkylene group, and m1 is an integer of 0 or more).
[0022] An embodiment [9] of the present disclosure is any one of the embodiments [1] to [8], in which the fibrous filler (A) is a cellulose fiber.
[0023] The present disclosure also includes, as embodiment
[10] , a method for producing a granule of any of the above embodiments [1] to [9], comprising a mixing step of mixing a precursor of the plant-derived fibrous filler (A), a precursor of the organic material (B), and water to obtain a mixture, and a granulation step of granulating the obtained mixture to obtain a granule.
[0024] The embodiment
[11] of the present disclosure is an embodiment in which, in the granulation step of the embodiment
[10] , the mixture is extrusion granulated.
[0025] The present disclosure also includes, as an embodiment
[12] , a resin composition comprising the granule of any one of the embodiments [1] to [9] above and a resin.
[0026] An embodiment
[13] of the present disclosure is an embodiment
[12] in which the resin is a thermoplastic resin.
[0027] The present disclosure also includes, as an embodiment
[14] , a method for producing a resin composition, comprising a resin kneading step of kneading the granules of any one of the embodiments [1] to [9] above with a resin.
[0028] The present disclosure also includes, as an embodiment
[15] , a molded article of the resin composition of embodiment
[12] or
[13] , the molded article being a part or material selected from automobile parts, electric / electronic parts, building materials, civil engineering materials, agricultural materials, packaging materials, living materials, and optical components.
[0029] The present disclosure also includes, as an embodiment
[16] , a rubber composition including the granule of any one of the embodiments [1] to [9] above and rubber.
[0030] The present disclosure also includes, as an aspect
[17] , a method for producing a rubber composition, comprising a rubber kneading step of kneading the granules of any one of the aspects [1] to [9] above with rubber.
[0031] The present disclosure also includes, as an embodiment
[18] , a molded article of the vulcanizate of the rubber composition of embodiment
[16] , which is a belt, a roll, a gasket, an oil seal, a packing, a hose, a window frame rubber, a vibration damping material, a carpet bagging material, an automotive part, a tire, or an electric wire coating.
[0032] In this specification and claims, the number of carbon atoms of a substituent is represented as C1, C6, C 10 For example, "C1 alkyl group" means an alkyl group with one carbon atom, and "C 6-10 The term "aryl group" refers to an aryl group having 6 to 10 carbon atoms.
[0033] Furthermore, in this specification and claims, when a numerical range is indicated using "~", it is intended to include both ends of the numerical range. Effect of the Invention
[0034] The present disclosure can provide granules that are excellent in handleability and feedability to a kneader, and that exhibit excellent dispersibility of a plant-derived fibrous filler in a resin or rubber. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0035] The granule (or granulated product) of the present disclosure is a fibrous filler (A) derived from a plant having an average fiber diameter of 0.5 to 100 μm, and an organic material (B) that is solid at room temperature and normal pressure and has a molecular weight of 100 to 1000, and has a bulk density of 0.1 to 0.5 g / cm. 3 Since the composition is adjusted to a concentration of 100% by weight, it has excellent handling properties and feedability to a kneader, and the plant-derived fibrous filler (A) can be uniformly dispersed in resins and rubbers. Furthermore, by using the granules of the present disclosure, the fibrous filler (A) can be uniformly dispersed in various resins and rubbers without preparing a master batch.
[0036] [Plant-derived fibrous filler (A)] The plant-derived fibrous filler (A) is a filler (filling agent or reinforcing agent) made from plants, and is not particularly limited as long as it is fibrous.
[0037] The plant raw material is not particularly limited, and examples thereof include wood, herbaceous plants, seed hairs, bamboo, sugarcane, etc. Examples of wood include conifers such as pine, fir, spruce, hemlock, and cedar, and broad-leaved trees such as beech, birch, poplar, and maple. Examples of herbaceous plants include hemp, flax, Manila hemp, ramie, and other hemp species; straw; bagasse; Mitsumata, etc. Examples of seed hairs include cotton linters, bombax cotton, and kapok.
[0038] The plant raw material may be waste paper, straw, food residue, etc. Examples of food residue include tea extract husks, coffee bean extract husks, grain husks, citrus peels, sugar cane meal, and bean skins.
[0039] These plant raw materials can be used alone or in combination of two or more. The plant raw material is preferably pulp with a low content of non-cellulose components such as lignin and hemicellulose. As the pulp, wood pulp such as coniferous pulp and hardwood pulp, seed hair fiber pulp such as cotton linter pulp, etc. are commonly used.
[0040] The fibrous filler (A) of the present disclosure is preferably formed from these plant raw materials, with cellulose fibers (fibrous cellulose) being particularly preferred.
[0041] The cellulose fibers may be highly crystalline, and the degree of crystallinity of the cellulose fibers is, for example, 40 to 100% (e.g., 50 to 100%), preferably 60 to 100%, more preferably 70 to 100%, and most preferably 75 to 99%, and usually the degree of crystallinity is 60% or more (e.g., 60 to 98%). Examples of the crystal structure of the cellulose fibers include type I, type II, type III, and type IV, and type I crystal structure, which is excellent in linear expansion properties and elastic modulus, is preferred. The degree of crystallinity can be measured using a powder X-ray diffractometer (Ultima IV, manufactured by Rigaku Corporation) or the like.
[0042] The cellulose fibers may contain non-cellulose components such as hemicellulose and lignin, and the proportion of the non-cellulose components in the fibrous cellulose is 30% by mass or less, preferably 20% by mass or less, and more preferably 10% by mass or less. The cellulose fibers may be cellulose fibers that are substantially free of non-cellulose components (particularly, cellulose fibers that do not contain non-cellulose components).
[0043] The degree of polymerization of the cellulose fibers may be 500 or more, and preferably 600 or more (for example, 600 to 100,000), from the viewpoint of the mechanical properties of the composition.
[0044] The average fiber diameter of the fibrous filler (A) (particularly cellulose fiber) may be 0.5 to 100 μm, but is preferably on the order of microns, for example, 1 to 80 μm, preferably 5 to 70 μm, more preferably 10 to 50 μm, and most preferably 30 to 45 μm. If the average fiber diameter is too small, when the granules are blended with resin or rubber and kneaded, the fibrous filler (A) may aggregate with each other, making it difficult to uniformly disperse the fibrous filler (A). Conversely, if the average fiber diameter is too large, when the granules are blended with resin or rubber and kneaded, the fibrous filler (A) may protrude from the surface of the kneaded product, degrading the appearance.
[0045] The average fiber length of the fibrous filler (A) (particularly cellulose fiber) can be selected from a range of about 1 μm or more (e.g., 1 μm to 100 mm), for example, 10 μm or more (e.g., 0.01 to 50 mm), preferably 100 μm or more (e.g., 0.1 to 30 mm), more preferably 300 μm or more (e.g., 0.3 to 20 mm), more preferably 500 μm or more (e.g., 0.5 to 10 mm), and most preferably 1 mm or more (e.g., 1 to 5 mm). If the average fiber length is too short, there is a risk that the mechanical properties cannot be sufficiently improved even if the granules are blended with resin or rubber, and conversely, if it is too long, there is a risk that it is difficult to uniformly disperse the fibrous filler (A) even if the granules are blended with resin or rubber.
[0046] The ratio (aspect ratio) of the average fiber length to the average fiber diameter of the fibrous filler (A) (particularly cellulose fiber) is, for example, 5 or more (e.g., 5 to 10,000), preferably 10 or more (e.g., 10 to 5,000), further preferably 15 or more (e.g., 15 to 3,000), more preferably 20 or more (e.g., 20 to 100), and most preferably 25 or more (e.g., 25 to 50). If the aspect ratio is too small, the reinforcing effect may decrease even if the granules are blended with resin or rubber, and if the aspect ratio is too large, uniform dispersion of the fibrous filler (A) may be difficult even if the granules are blended with resin or rubber.
[0047] In this specification and claims, the average fiber diameter, average fiber length and aspect ratio of the fibrous filler (A) (particularly, cellulose fiber) may be calculated by randomly selecting 50 fibers from an image of a scanning electron microscope photograph and averaging them. The average fiber diameter, average fiber length and aspect ratio of the fibrous filler (A) (particularly, cellulose fiber) are the average fiber diameter, average fiber length and aspect ratio of the fibrous filler (A) in the granules obtained by extrusion granulation.
[0048] The proportion of the fibrous filler (A) (particularly cellulose fiber) in the granules may be 10% by mass or more, for example, 10 to 99% by mass, preferably 30 to 95% by mass, further preferably 50 to 90% by mass, more preferably 60 to 85% by mass, and most preferably 70 to 80% by mass. If the proportion of the fibrous filler (A) is too low, even if the granules are blended with a resin or rubber, the reinforcing effect of the fibrous filler (A) is weakened, and there is a risk that the mechanical properties of the resin or rubber composition cannot be improved. If the proportion is too high, there is a risk that it becomes difficult to prepare the granules or the dispersibility of the fibrous filler (A) is reduced.
[0049] [Organic materials (B)] The granules of the present disclosure can ensure granulation properties by blending the fibrous filler (A) with an organic material (B).
[0050] Since the organic material (B) is solid at room temperature and normal pressure, it is easy to handle, granules can be easily prepared, and when the granules are blended with a resin or rubber, the dispersibility of the fibrous filler (A) can be improved, making it unnecessary to prepare a master batch for each resin or rubber. The room temperature may be 20°C, and the normal pressure may be atmospheric pressure (101.3 kPa).
[0051] The molecular weight of the organic material (B) is 100 to 1000, preferably 150 to 700, further preferably 200 to 500, more preferably 300 to 500, and most preferably 400 to 500. If the molecular weight is too small, when the granules are blended with a resin or rubber and kneaded, the organic material (B) volatilizes, and the fibrous filler (A) may not be uniformly dispersed. Conversely, if the molecular weight is too large, the compatibility of the granules with the resin or rubber may decrease.
[0052] The shape of the organic material (B) is not particularly limited, but may be non-fibrous, and is preferably granular (or powdery). The granular shape may be spherical, approximately spherical, ellipsoidal, polygonal or polyhedral, flat, rod-like or columnar, or irregular. Of these, the granular shape is preferably an isotropic shape such as a sphere, or an approximately isotropic shape such as an approximately spherical shape. Therefore, in the granular organic material, the ratio of the major axis to the minor axis (aspect ratio) is preferably close to 1, for example, 1 to 3, preferably 1 to 2, more preferably 1 to 1.5, more preferably 1 to 1.3, and most preferably 1 to 1.2.
[0053] The average particle size (D50) of the organic material (B) is, for example, 0.01 to 50 μm, preferably 0.1 to 30 μm, further preferably 0.5 to 20 μm, more preferably 1 to 10 μm, and most preferably 2 to 5 μm. If the average particle size of the organic material (B) is too small, it may be difficult to mix it uniformly with the fibrous filler (A), and conversely, if it is too large, it may be difficult to prepare a granule.
[0054] In this specification and claims, the average particle size of the organic material (B) can be measured by a conventional method, for example, it means the median particle size (D50) measured on a volume basis using a laser diffraction particle size distribution analyzer.
[0055] The organic material (B) is preferably a compound having a polar group because it can improve the affinity with the fibrous filler (A), and is particularly preferably a compound having a hydrophobic skeleton and a polar group because it is easy to handle.
[0056] Examples of polar groups include hydroxyl groups, carboxyl groups, acyl groups, alkoxy groups, glycidyloxy groups, amino groups, N-substituted amino groups, amide groups, mercapto groups, halogen atoms, and cyano groups. Examples of acyl groups include C groups such as acetyl groups and propionyl groups. 1-4 Alkyl-carbonyl groups and the like. Alkoxy groups include C methoxy groups, ethoxy groups, and the like. 1-4 Examples of N-substituted amino groups include N-mono C groups such as methylamino and ethylamino groups. 1-4 Examples of the polar group include an alkylamino group. Examples of the halogen atom include a fluorine atom, a chlorine atom, a bromine atom, and an iodine atom. These polar groups may be derivatives such as salts and esters. These polar groups may be used alone or in combination of two or more. Among these, a hydroxyl group, a carboxyl group, an amino group, and an amide group are preferred, and a hydroxyl group is particularly preferred. In the organic material (B), the number of polar groups in one molecule may be 1 or more, and is, for example, 1 to 6, preferably 1 to 4, more preferably 1 to 3, and more preferably 2.
[0057] Examples of the hydrophobic skeleton include aliphatic hydrocarbons, aromatic hydrocarbons, and alicyclic hydrocarbons.
[0058] Aliphatic hydrocarbons include C hexane, heptane, octane, decane, undecane, dodecane, pentadecane, and octadecane. 6-24 Alkanes; C such as hexene, octene, decene, undecene, dodecene, pentadecene, and octadecene6-24 These aliphatic hydrocarbons can be used alone or in combination of two or more. Among these, C 12-24 Alkanes are preferred.
[0059] Aromatic hydrocarbons include monocyclic arene rings such as benzene rings; condensed bicyclic C rings such as naphthalene rings; 10-16 Arene ring; fused tricyclic ring such as anthracene ring, phenanthrene ring, etc. 12-16 Arene rings; biphenyl rings, binaphthyl rings, phenylnaphthalene rings (1-phenylnaphthalene rings, 2-phenylnaphthalene rings, etc.) and other bi-C 6-12 Arene rings; terphenylene rings and other terphenylene rings 6-12 arene ring, fluorene ring, benzofluorene ring, dibenzofluorene ring, etc. These aromatic hydrocarbons can be used alone or in combination of two or more. Among these, fused bicyclic C rings such as benzene ring and naphthalene ring are preferred. 10-16 Arene ring; BiC such as biphenyl ring 6-10 An arene ring; a fluorene ring is preferred.
[0060] Examples of alicyclic hydrocarbons include hydrogenated aromatic hydrocarbons, as well as cyclopentane rings, cycloheptane rings, and tetralin rings. These alicyclic hydrocarbons can be used alone or in combination of two or more. Among these, C 6-10 A cycloalkane ring is preferred.
[0061] The hydrophobic skeleton may be at least one selected from the group consisting of aliphatic hydrocarbons, aromatic hydrocarbons, and alicyclic hydrocarbons, or may be a combination of two or more selected from the group consisting of aliphatic hydrocarbons, aromatic hydrocarbons, and alicyclic hydrocarbons.
[0062] When the hydrophobic skeleton is a combination of two or more selected from the group consisting of aliphatic hydrocarbons, aromatic hydrocarbons, and alicyclic hydrocarbons, the hydrocarbons may be linked together by a direct bond or through a linking group. Examples of the linking group include an alkylene group, an ether group (ether bond), a thioether group (sulfide group), and a sulfonyl group. Examples of the alkylene group of the linking group include C groups such as a methylene group, an ethylidene group, an ethylene group, and an isopropylidene group. 1-4 The combination of these hydrocarbons is not particularly limited as long as the molecular weight does not exceed 1000, but a combination of aromatic hydrocarbons is preferred, and a combination of a fluorene ring and at least one arene ring selected from the group consisting of a benzene ring, a naphthalene ring, and a biphenyl ring is particularly preferred.
[0063] Commonly used compounds having a hydrophobic skeleton and a polar group include fatty acids or derivatives thereof, bisphenols, and fluorene compounds.
[0064] Fatty acids include palmitic acid, stearic acid, hydroxystearic acid, arachidic acid, behenic acid, and montanic acid. 8-26 Saturated fatty acids; C such as oleic acid and erucic acid 8-26 Examples of fatty acid derivatives include fatty acid amides and fatty acid alkyl esters corresponding to these fatty acids. Examples of fatty acid alkyl esters include C esters such as methyl esters and ethyl esters. 1-4 Alkyl esters and the like.
[0065] Examples of bisphenols include 2,2-bis(4-hydroxyphenyl)propane (bisphenol A), 2,2-bis(4-hydroxyphenyl)butane (bisphenol B), 2,2-bis(3-methyl-4-hydroxyphenyl)propane (bisphenol C), 1,1-bis(4-hydroxyphenyl)ethane (bisphenol AD), bis(4-hydroxyphenyl)methane (bisphenol F), 2,2-bis(3-isopropyl-4-hydroxyphenyl)propane (bisphenol G), bis(4-hydroxyphenyl)sulfone (bisphenol S), and 1,1-bis(4-hydroxyphenyl)cyclohexane (bisphenol Z). Bisphenols are C-type bisphenols such as ethylene oxide. 2-4 The alkylene oxide may be an alkylene oxide adduct in which an alkylene oxide is added. The number of moles of alkylene oxide added is, for example, 1 to 10 moles, preferably 1 to 5 moles, and more preferably 1 to 3 moles.
[0066] (Organic materials containing polycyclic aromatic rings) In the granules of the present disclosure, when the granules are blended with a resin or rubber and kneaded, the fibrous filler (A) can be uniformly dispersed, and the mechanical properties such as the strength and elastic modulus of the resin composition or rubber composition after kneading can be improved. From these points of view, the organic material (B) is preferably an organic material containing a polycyclic aromatic ring (an organic material whose hydrophobic skeleton is a polycyclic aromatic ring), more preferably an organic material containing a fluorene ring, even more preferably a fluorene compound having aryl groups at the 9,9-position, and most preferably a compound represented by formula (1).
[0067] In the formula (1), examples of the arene ring represented by ring Z include monocyclic arene rings such as a benzene ring, and polycyclic arene rings. The polycyclic arene rings include fused polycyclic arene rings (fused polycyclic hydrocarbon rings) and ring-assembled arene rings (ring-assembled aromatic hydrocarbon rings).
[0068] The fused polycyclic arene ring includes, for example, a fused bicyclic arene ring (e.g., a fused bicyclic C ring such as a naphthalene ring). 10-16Examples of the fused polycyclic arene ring include fused bicyclic to tetracyclic arene rings such as fused tricyclic arene rings (e.g., anthracene ring, phenanthrene ring, etc.). Examples of the fused polycyclic arene ring include a naphthalene ring and an anthracene ring, and a naphthalene ring is particularly preferred.
[0069] Examples of the ring-assembled arene ring include biarene rings [e.g., biphenyl rings, binaphthyl rings, phenylnaphthalene rings (e.g., 1-phenylnaphthalene rings, 2-phenylnaphthalene rings, etc.) 6-12 arene rings, etc.], terarene rings (e.g., terphenylene rings, etc.) 6-12 Examples of preferred ring-assembly arene rings include biC 6-10 Examples include an arene ring, particularly a biphenyl ring.
[0070] The two rings Z substituted at the 9-position of fluorene may be different or the same, but are usually the same ring in many cases. Among the rings Z, a benzene ring, a naphthalene ring, a biphenyl ring (particularly a benzene ring), etc. are preferred.
[0071] The substitution position of the ring Z at the 9-position of the fluorene is not particularly limited. For example, when the ring Z is a naphthalene ring, the group corresponding to the ring Z at the 9-position of the fluorene may be a 1-naphthyl group, a 2-naphthyl group, or the like.
[0072] X 1 Examples of the heteroatom-containing functional group represented by the formula (1) include functional groups having at least one heteroatom selected from oxygen, sulfur, and nitrogen atoms. The number of heteroatoms contained in such functional groups is not particularly limited, but may usually be 1 to 3, and preferably 1 or 2.
[0073] The functional group may be, for example, a group -[(OA) m1 -Y 1 ](where, Y 1is a hydroxyl group, a glycidyloxy group, an amino group, an N-substituted amino group or a mercapto group, A is an alkylene group, and m1 is an integer of 0 or more), a group -(CH2) m2 -COOR 3 (In the formula, R 3 is a hydrogen atom or an alkyl group, and m2 is an integer of 0 or more.
[0074] Group - [(OA) m1 -Y 1 ], Y 1 Examples of the N-substituted amino group include N-monoalkylamino groups (N-monoC groups) such as methylamino and ethylamino groups. 1-4 N-monohydroxyalkylamino groups (N-monohydroxyC alkylamino groups, etc.), hydroxyethylamino groups, etc. 1-4 alkylamino groups, etc.
[0075] The alkylene group A includes linear or branched alkylene groups. Examples of the linear alkylene group include C alkylene groups such as ethylene, trimethylene, and tetramethylene. 2-6 Alkylene group (preferably linear C 2-4 Alkylene groups, more preferably linear C 2-3 Examples of the branched alkylene group include branched C alkylene groups such as propylene, 1,2-butanediyl, and 1,3-butanediyl. 3-6 Alkylene group (preferably branched C 3-4 alkylene groups, particularly propylene groups).
[0076] m1, which indicates the number of repetitions (average number of moles added) of the oxyalkylene group (OA), can be selected from the range of 0 or more (for example, 0 to 15, preferably 0 to 10), and may be, for example, 0 to 8 (for example, 1 to 8), preferably 0 to 5 (for example, 1 to 5), more preferably 0 to 4 (for example, 1 to 4), particularly 0 to 3 (for example, 1 to 3), and may usually be 0 to 2 (for example, 0 to 1). When m1 is 2 or more, the types of alkylene groups A may be the same or different. Furthermore, the types of alkylene groups A in the same or different rings Z may be the same or different.
[0077] Group-(CH2) m2 -COOR 3 In R 3 The alkyl group represented by the formula (I) is a straight-chain or branched C alkyl group such as a methyl group, an ethyl group, a propyl group, an isopropyl group, a butyl group, or a t-butyl group. 1-6 Examples of the alkyl group include the alkyl group C 1-4 Alkyl groups, especially C 1-2 It is an alkyl group. m2, which indicates the number of repeating methylene groups (average number of moles added), is preferably 1 to 6, more preferably 1 to 4, and even more preferably 1 to 2. m2 may usually be 0 or 1 to 2.
[0078] Among these, the group X is preferred because it can greatly improve the dispersibility of the fibrous filler (A). 1 is Y 1 is a hydroxyl group -[(OA) m1 -OH] [wherein A is an ethylene group or the like C 2-6 Alkylene groups (e.g., C 2-4 Alkylene groups, especially C 2-3 alkylene group), and m1 is an integer of 0 to 5 (for example, 0 or 1).
[0079] In the formula (1), the group X substituted on the ring Z 1 The number n is 1 or more, preferably 1 to 3, and more preferably 1 or 2 (particularly 1). The number n of substitutions in each ring Z may be the same or different.
[0080] Group X 1 can be substituted at an appropriate position of ring Z. For example, when ring Z is a benzene ring, it is often substituted at at least one selected from the group consisting of 2-, 3- and 4-positions of the phenyl group (particularly, 3- and / or 4-positions, especially 4-position). When ring Z is a naphthalene ring, it is often substituted at any one of the 5- to 8-positions of the naphthyl group. For example, the 9-position of fluorene is substituted at the 1- or 2-position of the naphthalene ring (substitution in a 1-naphthyl or 2-naphthyl relationship), and the group X can be substituted at the 1,5-position, 2,6-position, etc. relationship (particularly when n is 1, 2,6-position relationship) with respect to this substitution position. 1 In addition, when n is 2 or more, the substitution position is not particularly limited. In addition, in the ring assembly arene ring Z, the group X 1 The substitution position of is not particularly limited, and may be substituted, for example, on the arene ring bonded to the 9-position of the fluorene and / or on the arene ring adjacent to this arene ring. For example, the 3- or 4-position of the biphenyl ring Z may be bonded to the 9-position of the fluorene, and when the 3-position of the biphenyl ring Z is bonded to the 9-position of the fluorene, the group X 1 The substitution position may be any of the 2-position, 4-position, 5-position, 6-position, 2'-position, 3'-position, and 4'-position, and is preferably the 6-position.
[0081] In the formula (1), the substituent R 2 Examples of the alkyl group include linear or branched C alkyl groups such as halogen atoms (e.g., fluorine, chlorine, bromine, and iodine atoms), alkyl groups (methyl, ethyl, propyl, isopropyl, butyl, s-butyl, and t-butyl groups), and the like. 1-10 Alkyl groups, preferably linear or branched C 1-6 Alkyl groups, more preferably linear or branched C 1-4 alkyl group, cycloalkyl group (cyclopentyl group, cyclohexyl group, etc.) 5-10 Cycloalkyl groups, aryl groups [phenyl groups, alkylphenyl groups (methylphenyl (tolyl) groups, dimethylphenyl (xylyl) groups, etc.), biphenyl groups, naphthyl groups, etc. 6-12aryl group], aralkyl group (benzyl group, phenethyl group, etc.) 6-10 Aryl-C 1-4 Alkyl groups, etc.), alkoxy groups (e.g., methoxy, ethoxy, propoxy, n-butoxy, isobutoxy, t-butoxy, and other linear or branched C 1-10 alkoxy groups, cycloalkoxy groups (e.g., cyclohexyloxy groups, etc.) 5-10 cycloalkoxy groups, aryloxy groups (e.g., phenoxy groups, etc.) 6-10 aryloxy groups, aralkyloxy groups (e.g., C 6-10 Aryl-C 1-4 alkyloxy groups, alkylthio groups (e.g., methylthio, ethylthio, propylthio, n-butylthio, t-butylthio, etc.) 1-10 alkylthio groups, cycloalkylthio groups (e.g., cyclohexylthio groups, etc.) 5-10 cycloalkylthio groups, arylthio groups (e.g., thiophenoxy groups, etc.) 6-10 arylthio groups, aralkylthio groups (e.g., benzylthio groups, etc.) 6-10 Aryl-C 1-4 alkylthio groups, acyl groups (e.g., acetyl groups, etc.) 1-6 acyl group, a nitro group, a cyano group, etc.
[0082] These substituents R 2 Representative examples of the substituent R include a halogen atom, a hydrocarbon group (an alkyl group, a cycloalkyl group, an aryl group, an aralkyl group), an alkoxy group, an acyl group, a nitro group, a cyano group, and a substituted amino group. 2 The alkyl groups, alkoxy groups (such as methoxy groups) and linear or branched C 1-4 Alkoxy groups, in particular linear or branched C alkyl groups such as methyl groups 1-4 The substituent R is preferably an alkyl group. 2 is an aryl group, the substituent R 2may form the ring assembly arene ring together with the ring Z. 2 The types of may be the same or different in the same or different rings Z.
[0083] Substituent R 2 The coefficient p can be appropriately selected depending on the type of ring Z, and may be, for example, an integer of about 0 to 8, an integer of 0 to 4, preferably an integer of 0 to 3 (e.g., 0 to 2), and more preferably 0 or 1. In particular, when p is 1, ring Z is a benzene ring, a naphthalene ring, or a biphenyl ring, and the substituent R 2 may be a methyl group.
[0084] Substituent R 1 Examples of the alkyl group include a cyano group, a halogen atom (such as a fluorine atom, a chlorine atom, or a bromine atom), a carboxyl group, and an alkoxycarbonyl group (such as a methoxycarbonyl group). 1-4 Alkoxy-carbonyl group, alkyl group (methyl group, ethyl group, propyl group, isopropyl group, butyl group, t-butyl group, etc.) 1-6 C alkyl groups, aryl groups (phenyl groups, etc. 6-10 Aryl groups).
[0085] These substituents R 1 Of these, linear or branched C 1-4 Alkyl groups (especially C groups such as methyl groups) 1-3 alkyl group), carboxyl group or C 1-2 An alkoxy-carbonyl group, a cyano group, or a halogen atom is preferred. The number of substitutions k is an integer of 0 to 4 (e.g., 0 to 3), preferably an integer of 0 to 2 (e.g., 0 or 1), and particularly 0. The numbers of substitutions k may be the same or different from each other. When k is 2 or more, the substituent R 1 The types of the substituents R substituted on the two benzene rings of the fluorene ring may be the same or different. 1 The types of the substituents R may be the same or different. 1The substitution position of is not particularly limited, and may be, for example, the 2-position to the 7-position (such as the 2-position, the 3-position and / or the 7-position) of the fluorene ring.
[0086] Among these, preferred fluorene compounds are, for example, 9,9-bis(hydroxyC) such as 9,9-bis(4-hydroxyphenyl)fluorene, 9,9-bis(5-hydroxy-1-naphthyl)fluorene, and 9,9-bis(6-hydroxy-2-naphthyl)fluorene. 6-12 9,9-bis(di- or trihydroxyphenyl)fluorene, such as 9,9-bis(3,4-dihydroxyphenyl)fluorene; 6-12 aryl)fluorene; 9,9-bis(mono or di C such as 9,9-bis(3-methyl-4-hydroxyphenyl)fluorene and 9,9-bis(3,5-dimethyl-4-hydroxyphenyl)fluorene 1-4 Alkyl-Hydroxy C 6-12 aryl)fluorene; 9,9-bis(C 6-12 Aryl-Hydroxy C 6-12 aryl)fluorene; 9,9-bis(hydroxy(poly)C such as 9,9-bis[4-(2-hydroxyethoxy)phenyl]fluorene and 9,9-bis[6-(2-hydroxyethoxy)-2-naphthyl]fluorene 2-4 Alkoxy-C 6-12 9,9-bis(mono or di C aryl)fluorene; 9,9-bis[3-methyl-4-(2-hydroxyethoxy)phenyl]fluorene, etc. 1-4 Alkyl-hydroxy(poly)C 2-4 Alkoxy-C 6-12 aryl)fluorene; 9,9-bis(C aryl)fluorene such as 9,9-bis[3-phenyl-4-(2-hydroxyethoxy)phenyl]fluorene and 9,9-bis[4-phenyl-3-(2-hydroxyethoxy)phenyl]fluorene; 6-12 Aryl-hydroxy(poly)C 2-4 Alkoxy-C 6-12Particularly preferred fluorene compounds include 9,9-bis(hydroxy(poly)C such as 9,9-bis[4-(2-hydroxyethoxy)phenyl]fluorene (BPEF). 2-4 9,9-bis(hydroxy(poly)C such as alkoxy-phenyl)fluorene and 9,9-bis[6-(2-hydroxyethoxy)-2-naphthyl]fluorene (BNEF) 2-4 9,9-bis(phenyl-hydroxy(poly)C such as alkoxy-naphthyl)fluorene and 9,9-bis[4-(2-hydroxyethoxy)-3-phenylphenyl]fluorene (BOPPEF) 2-4 alkoxy-phenyl)fluorene, most preferably 9,9-bis(hydroxy(poly)C such as BPEF 2-4 alkoxy-phenyl)fluorene.
[0087] These fluorene compounds can be used alone or in combination of two or more. Note that the term "(poly)alkoxy" is used to mean both an alkoxy group and a polyalkoxy group.
[0088] The proportion of the fluorene compound represented by the formula (1) in the organic material (B) may be 50% by mass or more, preferably 80% by mass or more, more preferably 90% by mass or more, and most preferably 100% by mass.
[0089] (Characteristics of organic material (B)) The organic material (B) may be crystalline or amorphous. When the organic material (B) is crystalline, the melting point of the organic material (B) may be a melting point that allows melt kneading, but may be 100°C or higher (for example, 100 to 250°C), for example, 120 to 230°C, preferably 130 to 200°C, particularly preferably 135 to 180°C, further preferably 140 to 170°C, more preferably 145 to 165°C, and most preferably 150 to 163°C. When the organic material (B) is amorphous, it may be meltable (or flowable) within the above melting point range. If the melting point of the organic material (B) is too low, it may not be possible to maintain a solid state, making it difficult to produce granules, and conversely, if it is too high, it may be difficult to handle.
[0090] In this specification and claims, the melting point of the organic material (B) means the peak top temperature in a differential scanning calorimetry (DSC) curve.
[0091] In order to easily disperse the fibrous filler (A) uniformly in the resin or rubber during the kneading process of the granules with the resin or rubber, the organic material (B) is preferably in a state where it is not complexed (chemically modified) with the fibrous filler (A) by forming a covalent bond such as an ether bond or an ester bond. When the organic material (B) and the fibrous filler (A) are complexed, it is preferable that they are complexed by relatively loose bonding or affinity through hydrogen bonding or the like. When complexed through loose bonding, it can be estimated that the degree of freedom of the fibrous filler (A) in the resin or rubber composition is high, and the mechanical properties (such as bending fatigue resistance) of the resin or rubber composition can be improved.
[0092] The proportion of the organic material (B) [particularly the fluorene compound represented by the formula (1)] is, for example, 1 to 70 parts by mass, preferably 5 to 50 parts by mass, more preferably 10 to 45 parts by mass, more preferably 20 to 40 parts by mass, and most preferably 30 to 35 parts by mass, relative to 100 parts by mass of the fibrous filler (A). If the proportion of the organic material (B) is too small, it may be difficult to prepare the granules or the dispersibility of the fibrous filler (A) may decrease, whereas if it is too large, the reinforcing effect of the fibrous filler (A) may be weakened, and the mechanical properties of the resin or rubber composition may not be improved.
[0093] (Other ingredients) The granules of the present disclosure may further contain conventional additives. Conventional additives include adhesives, pressure sensitive adhesives, adhesion improvers, tackifiers, silane coupling agents, softeners, crosslinking agents, crosslinking assistants, reinforcing agents, plasticizers, aging or oxidation inhibitors, colorants, stabilizers, release agents, lubricants, flame retardants, vibration damping agents, flame retardant assistants, antistatic agents, conductive agents, flow regulators, leveling agents, defoamers, surface modifiers, stress reducing agents, nucleating agents, crystallization promoters, antibacterial agents, and preservatives.
[0094] These additives can be used alone or in combination of two or more. The total proportion of these additives may be 50 parts by mass or less, for example, 0.01 to 50 parts by mass, preferably 0.1 to 30 parts by mass, and more preferably 1 to 10 parts by mass, based on 100 parts by mass of the fibrous filler (A).
[0095] [Characteristics of granules] The shape of the granules of the present disclosure is not particularly limited, but granular (or powdery) is preferred. The granules may be spherical, approximately spherical, ellipsoidal, polygonal or polyhedral, flat, rod-like or columnar, or irregular. Of these, the granules are preferably isotropic, such as spherical, or approximately isotropic, such as approximately spherical or cylindrical. Therefore, in the granules, the ratio of the major axis to the minor axis (aspect ratio) is preferably close to 1, for example, 1 to 3, preferably 1 to 2, more preferably 1 to 1.5, more preferably 1 to 1.3, and most preferably 1 to 1.2. When the granules are cylindrical, the major axis corresponds to the larger of the height of the cylinder and the diameter of the circular bottom surface, and the minor axis corresponds to the smaller of the height of the cylinder and the diameter of the circular bottom surface.
[0096] The average particle size (D50) of the granules is, for example, 0.1 to 20 mm, preferably 1 to 10 mm, further preferably 1.5 to 5 mm, more preferably 2 to 4 mm, and most preferably 2.5 to 3.5 mm. If the average particle size of the granules is too small, it may be difficult to mix uniformly with the fibrous filler (A), and conversely, if it is too large, it may be difficult to prepare the granules.
[0097] In this specification and claims, the average particle size of the granules can be measured by a conventional method, for example, 50 particles are randomly selected from an image taken using a scanning electron microscope, and the average particle size may be calculated.
[0098] The bulk density of the granules of the present disclosure is 0.1 to 0.5 g / cm 3 and preferably 0.13 to 0.4 g / cm 3 , and more preferably 0.15 to 0.3 g / cm3 , more preferably 0.18 to 0.25 g / cm 3 , and most preferably 0.19 to 0.23 g / cm 3 If the bulk density is too small, when the granules are mixed with resin or rubber, there is a risk that the granules will not be caught in the kneader screw as much, making it impossible to feed them stably, whereas if the bulk density is too large, the granules will be too compacted, making it difficult to disperse them in the kneader.
[0099] In this specification and claims, the bulk density of the granules can be determined by measuring the volume and mass using a measuring cylinder, and in detail, can be measured by the method described in the examples below.
[0100] [Method of manufacturing granules] The granules of the present disclosure are obtained through a mixing step in which a precursor of a plant-derived fibrous filler (A), a precursor of an organic material (B), and water are mixed to obtain a mixture, and a granulation step in which the mixture is granulated to obtain a granule. In the present disclosure, the precursors are easily mixed uniformly by using water in the mixing step, and the safety is also high.
[0101] In the mixing step, the proportion of water is, for example, 10 to 500 parts by mass, preferably 50 to 300 parts by mass, further preferably 100 to 250 parts by mass, more preferably 130 to 200 parts by mass, and most preferably 150 to 180 parts by mass, relative to 100 parts by mass of the precursor of the plant-derived fibrous filler (A). If the proportion of water is too low, it may be difficult to uniformly mix the precursor of the plant-derived fibrous filler (A) and the precursor of the organic material (B), whereas if the proportion is too high, the productivity of the granules may decrease.
[0102] The precursors may be mixed (or stirred) by a conventional mixing or stirring means, for example, at a rotation speed of about 100 to 10,000 rpm, preferably 500 to 5,000 rpm, more preferably 1,000 to 3,000 rpm, and particularly preferably 1,500 to 2,500 rpm.
[0103] Examples of conventional mixing or stirring methods include methods using a ball mill, a tumble mixer, a ribbon blender, a Henschel mixer, a mixing roller, a kneader, a Banbury mixer, an extruder (such as a single-screw or twin-screw extruder), and the like.
[0104] The mixing time is, for example, 1 to 100 minutes, preferably 3 to 60 minutes, and more preferably 5 to 30 minutes.
[0105] In the granulation step, the granulation method can be selected from conventional granulation methods such as rolling granulation, fluidized bed granulation, stirring granulation, crushing granulation, compression granulation, extrusion granulation, and dissolution granulation. Among these, compression granulation and extrusion granulation are preferred, and extrusion granulation is particularly preferred because it is easy to produce granules having the desired bulk density. Extrusion granulation can be performed using a conventional extrusion granulator such as a disk pelleter.
[0106] The granulation temperature can be selected within the range of room temperature to about 200°C, but is preferably room temperature to 100°C, and more preferably room temperature to 50°C. Since the temperature may increase due to kneading, for convenience, granulation may usually be performed at room temperature in an unheated state.
[0107] The obtained granules may be subjected to a drying step. In the drying step, the drying method may be natural drying, but from the viewpoint of productivity, it is preferable to dry by heating. The heating temperature is, for example, 50 to 200°C, preferably 60 to 150°C, and more preferably 80 to 120°C. The drying time is, for example, 1 to 24 hours, preferably 3 to 15 hours, and more preferably 5 to 10 hours.
[0108] [Resin composition] The resin composition of the present disclosure includes the granules and a resin. The granules are granular and have a specific bulk density, and therefore are easy to handle. For example, when the granules and a resin are kneaded to prepare a resin composition, the granules can be smoothly fed to a kneader via a feeder or the like, and the aggregation of the fibrous filler (A) contained in the granules can be suppressed even when kneaded with the resin. Therefore, the fibrous filler (A) can be uniformly dispersed in the resin composition, and the mechanical properties of the resin composition can be improved.
[0109] (resin) The resin may be a curable resin (thermo- or photo-curable resin) or a thermoplastic resin.
[0110] Examples of curable resins include phenolic resins such as resol-type phenolic resins and novolac-type phenolic resins; amino resins such as urea resins, melamine resins, and guanamine resins; furan resins; unsaturated polyester resins; diallyl phthalate resins; vinyl ester resins (or epoxy (meth)acrylate resins); multifunctional (meth)acrylate resins; epoxy resins; urethane resins; polyimide resins such as bismaleimide resins; and silicone resins.
[0111] Thermoplastic resins include polyolefin resins such as linear olefin resins and cyclic olefin resins; styrene resins such as polystyrene, styrene-methyl methacrylate copolymer (MS resin), styrene-acrylonitrile copolymer (AS resin), high impact polystyrene (HIPS), acrylonitrile-butadiene-styrene copolymer (ABS resin), and methyl methacrylate-butadiene-styrene copolymer (MBS resin); and (meth)acrylic acid-(meth)acrylic acid ester copolymers. ) Acrylic resins; vinyl acetate resins such as polyvinyl acetate (PVAc), polyvinyl alcohol (PVA), polyvinyl acetal (polyvinyl formal (PVF), polyvinyl butyral (PVB), etc.); vinyl chloride homopolymers (PVC); vinyl chloride resins such as vinyl chloride-vinyl acetate copolymers; vinylidene chloride resins such as vinylidene chloride-vinyl chloride copolymers and vinylidene chloride-acrylonitrile copolymers; fluororesins such as polytetrafluoroethylene (PTFE); polyalkylene arylate resins, polyarylate resins Polyester-based resins such as polyester, liquid crystal polyester (LCP); polycarbonate-based resins such as bisphenol A polycarbonate-based resin; polyamide-based resins such as aliphatic polyamide resin, aromatic polyamide resin, or aramid resin; polyacetal-based resins such as polyacetal resin (POM); polyphenylene ether-based resins such as polyphenylene ether (PPE); polyether ketone-based resins such as polyether ketone (PEK), polyether ether ketone (PEEK), and polyether ketone ether ketone ketone (PEKEKK) Resins; phenoxy resins; polyketone resins such as aliphatic polyketone resins; polyphenylene sulfide resins such as polyphenylene sulfide (PPS); polysulfone resins such as polysulfone (PSF) and polyethersulfone (PES); cellulose esters such as nitrocellulose, cellulose acetate, and cellulose acetate propionate; cellulose ethers such as ethyl cellulose and carboxymethyl cellulose; thermoplastic polyimide resins such as polyetherimide (PEI) and polyamideimide; polyether nitrile resins;Examples of thermoplastic elastomers include polystyrene-based thermoplastic elastomers (TPEs), polyolefin-based TPEs (TPOs), polydiene-based TPEs, chlorine-based TPEs, fluorine-based TPEs, polyurethane-based TPEs (TPUs), polyester-based TPEs (TPEEs), and polyamide-based TPEs (TPAs).
[0112] These resins can be used alone or in combination of two or more kinds. Among these, thermoplastic resins are preferred.
[0113] The density of the thermoplastic resin is, for example, 0.85 to 3 g / cm 3 For example, the range may be selected from 0.9 to 2.7 g / cm 3 , preferably 0.95 to 2 g / cm 3 , and more preferably 0.95 to 1.5 g / cm 3 may be also possible.
[0114] The weight average molecular weight Mw of the thermoplastic resin may be selected, for example, from the range of about 10,000 to 10,000,000. The number average molecular weight Mn may be selected, for example, from the range of about 10,000 to 1,000,000, preferably 50,000 to 800,000, preferably 100,000 to 500,000, and more preferably 200,000 to 400,000. The molecular weight distribution (Mw / Mn) may be selected, for example, from the range of about 1 to 50, for example, 2 to 25.
[0115] In the present specification and claims, the weight average molecular weight, number average molecular weight and molecular weight distribution can be measured by GPC in terms of standard polystyrene.
[0116] Among the thermoplastic resins, it is preferable to include at least one selected from polyolefin-based resins, polyacetal-based resins, polyester-based resins and polyamide resins, and polyolefin-based resins are particularly preferable.
[0117] (Polyolefin resin) Examples of polyolefin resins include linear olefin resins containing α-olefin as a main polymerization component, and cyclic olefin resins containing cyclic olefins as polymerization components (cyclic olefin copolymers (COC) such as ethylene-norbornene copolymers, addition or ring-opening polymers of cyclic olefins such as polynorbornene, polydicyclopentadiene, polycyclopentadiene, or hydrogenated products thereof, or hydrogenated products thereof). Of these, linear olefin resins are preferred.
[0118] Examples of α-olefins, which are polymerization components of linear olefin resins, include α-C ethylene, propylene, 1-butene, 1-pentene, 3-methyl-1-butene, 1-hexene, 3-methyl-1-pentene, 4-methyl-1-pentene, 1-heptene, 4-methyl-1-hexene, 4,4-dimethyl-1-pentene, 3-ethyl-1-pentene, 1-octene, 4,4-dimethyl-1-hexene, 3-ethyl-1-hexene, 4-ethyl-1-hexene, 1-decene, 1-dodecene, 1-tetradecene, 1-hexadecene, 1-octadecene, and 1-eicosene. 2-20 Olefins and the like.
[0119] These α-olefins can be used alone or in combination of two or more. 2-10 Olefins are preferred, and α-C such as ethylene and propylene are preferred. 2-6 Olefins are particularly preferred.
[0120] The chain olefin resin may be a homopolymer or a copolymer of the α-olefin. The polymerization components in the copolymer may contain two or more kinds of α-olefins, or may contain a copolymerizable monomer different from the α-olefin. The copolymer may be a random copolymer, a block copolymer, or the like.
[0121] The copolymerizable monomer includes (meth)acrylic acid C such as (meth)acrylic acid, methyl (meth)acrylate, and ethyl (meth)acrylate. 1-10Examples of the monomers include (meth)acrylic monomers such as alkyl esters, glycidyl (meth)acrylate, (meth)acrylamide, and (meth)acrylonitrile; unsaturated carboxylic acids or their anhydrides such as maleic acid, fumaric acid, itaconic acid, citraconic acid, crotonic acid, isocrotonic acid, mesaconic acid, angelic acid, and their anhydrides; vinyl carboxylate esters such as vinyl acetate and vinyl propionate; non-conjugated alkadienes such as 1,4-hexadiene, 1,7-octadiene, 4-methyl-1,4-hexadiene, and 5-methyl-1,4-hexadiene; and conjugated alkadienes such as butadiene and isoprene.
[0122] These copolymerizable monomers can be used alone or in combination of two or more. When a chain olefin resin such as a polyethylene resin contains a copolymerizable monomer, the ratio of the copolymerizable monomer to the total constitutional units may be about 70 mol% or less, and is usually 50 mol% or less, for example, 30 mol% or less (e.g., 0.01 to 30 mol%), preferably 20 mol% or less (e.g., 0.1 to 20 mol%), and more preferably 10 mol% or less (e.g., 1 to 10 mol%).
[0123] Representative chain olefin resins include poly α-C resins such as polyethylene resins, polypropylene resins, poly-1-butene resins, and poly-4-methyl-1-pentene resins. 2-6 Examples of the resin include olefin resins, and polyethylene resins and polypropylene resins are preferred, with polyethylene resins being particularly preferred.
[0124] Examples of polyethylene resins include polyethylenes such as low-density polyethylene (LDPE), medium-density polyethylene (MDPE), high-density polyethylene (HDPE), linear low-density polyethylene (LLDPE), and ultra-high molecular weight polyethylene (UHMWPE); ethylene-propylene copolymers, ethylene-(1-butene) copolymers, ethylene-propylene-(1-butene) copolymers, and ethylene-(4-methyl-1-pentene) copolymers; 3-10olefin copolymers; modified polyethylenes such as maleic anhydride modified polyethylene; chlorinated polyethylene; ionomers, etc.
[0125] These polyethylene resins can be used alone or in combination of two or more. Among these polyethylene resins, linear polyethylenes with almost no branched structure such as HDPE, LLDPE, and UHMWPE are preferred, and from the viewpoint of the mechanical properties of the resin composition, HDPE and UHMWPE are particularly preferred, with HDPE being particularly preferred.
[0126] The density of polyethylene resin is 0.910 to 0.980 kg / m according to JIS K 6922-1. 3 From the viewpoint of excellent mechanical properties of the resin composition, for example, 0.930 to 0.970 kg / m 3 , preferably 0.940 to 0.965 kg / m 3 , and more preferably 0.950 to 0.962 kg / m 3 , more preferably 0.955 to 0.960 kg / m 3 It is.
[0127] The melt mass flow rate (MFR) of the polyethylene resin is, for example, 3 to 80 g / 10 min, preferably 5 to 50 g / 10 min, more preferably 10 to 30 g / 10 min, and even more preferably 15 to 25 g / 10 min, in accordance with JIS K 6922-2. If the MFR is too small, the melt moldability of the resin composition may decrease, whereas if the MFR is too large, the mechanical properties of the resin composition may decrease.
[0128] The melting point (DSC method) of the polyethylene resin is, in accordance with ISO 11357-3, for example, 80 to 150° C., preferably 100 to 145° C., further preferably 120 to 140° C., and even more preferably 130 to 135° C. If the melting point is too low, the heat resistance of the resin composition may decrease, whereas if the melting point is too high, the melt moldability of the resin composition may decrease.
[0129] (Polyacetal resin) Polyacetal resins include polyacetal homopolymers (single polymers) consisting essentially of repeating oxymethylene units (-CHO-) and polyacetal copolymers (copolymers) containing oxymethylene units and at least one type of copolymerizable monomer (comonomer) unit. Polyacetal resins may be homopolymers (single polymers), but are often copolymers (copolymers) because of their excellent thermal stability and their wide range of applications.
[0130] The polyacetal copolymer (copolymer) may be a copolymer composed of two components, a terpolymer composed of three components, etc. The polyacetal copolymer (copolymer) may be a random copolymer, a block copolymer, a graft copolymer, etc.
[0131] The comonomer units of the copolymer include oxyC 2-6 Alkylene units (e.g., oxyethylene group (-OCH2CH2-), oxypropylene group, oxytetramethylene group, etc.) 2-4 alkylene units, etc.
[0132] These comonomer units can be used alone or in combination of two or more kinds. The proportion of the comonomer units is, for example, 0.01 to 30 mol %, preferably 0.03 to 20 mol %, and more preferably 0.03 to 15 mol %, based on the entire polyacetal resin.
[0133] Specifically, the polyacetal resin may be a homopolymer or copolymer containing, as a main polymerization component, an aldehyde such as formaldehyde, paraformaldehyde, or acetaldehyde, or a cyclic ether or cyclic formal such as trioxane, ethylene oxide, propylene oxide, 1,3-dioxolane, 1,3-dioxane, diethylene glycol formal, or 1,4-butanediol formal.
[0134] The polyacetal resin may contain other copolymerization components, such as alkyl or aryl glycidyl ethers, such as methyl glycidyl ether, ethyl glycidyl ether, phenyl glycidyl ether, and naphthyl glycidyl ether; alkylene or polyalkylene glycol diglycidyl ethers, such as ethylene glycol diglycidyl ether, triethylene glycol diglycidyl ether, and butanediol diglycidyl ether; alkyl or aryl glycidyl alcohols; cyclic esters, such as β-propiolactone; and vinyl compounds, such as vinyl ethers.
[0135] The polyacetal resin may have a linear or branched structure or may be crosslinked. The terminals of the polyacetal resin may be stabilized by, for example, esterification with a carboxylic acid such as acetic acid or propionic acid or an anhydride thereof, urethane formation with an isocyanate compound, or etherification.
[0136] These polyacetal resins can be used alone or in combination of two or more.
[0137] The density of polyacetal resins is 0.95 to 1.8 g / cm according to ISO 1183. 3 In view of excellent mechanical properties of the resin composition, for example, 1 to 1.75 g / cm 3 ), preferably 1.1 to 1.73 g / cm 3 , and more preferably 1.2 to 1.7 g / cm 3 , more preferably 1.3 to 1.5 g / cm 3 It is.
[0138] The melt mass flow rate (MFR) of the polyacetal resin is, for example, 5 to 100 g / 10 min, preferably 10 to 80 g / 10 min, more preferably 30 to 60 g / 10 min, and even more preferably 40 to 50 g / 10 min, according to ISO 1133 (190°C, 2.16 kg load). If the MFR is too small, the melt moldability of the resin composition may decrease, whereas if the MFR is too large, the mechanical properties of the resin composition may decrease.
[0139] The deflection temperature under load of the polyacetal resin is, in accordance with ISO 75-1,2, for example, 60 to 200° C., preferably 70 to 150° C., further preferably 80 to 130° C., and even more preferably 90 to 110° C. If the deflection temperature under load is too low, the heat resistance of the resin composition may decrease, whereas if it is too high, the melt moldability of the resin composition may decrease.
[0140] (Polyester resin) Examples of polyester-based resins include polyesters obtained by reacting (condensing) a diol component with a dicarboxylic acid component.
[0141] Examples of the diol component include aliphatic diols such as alkanediols and polyalkanediols; alicyclic diols such as cycloalkanediols and di(hydroxyalkyl)cycloalkanes; and aromatic diols such as dihydroxyarenes, aromatic aliphatic diols, and bisphenols.
[0142] Examples of alkanediols include C alkanediols such as ethylene glycol, 1,2-propanediol, 1,3-propanediol, 1,4-butanediol, 1,2-butanediol, 1,3-butanediol, 1,4-pentanediol, 1,5-pentanediol, 1,3-pentanediol, and neopentyl glycol. 2-10 Alkanediols and the like.
[0143] The polyalkanediols include di- or tri-C such as diethylene glycol, dipropylene glycol, and triethylene glycol. 2-4Alkanediols and the like.
[0144] Cycloalkanediols include C 5-8 Cycloalkanediols and the like.
[0145] Di(hydroxyalkyl)cycloalkanes include di(hydroxy C) such as cyclopentane dimethanol and cyclohexane dimethanol. 1-4 Alkyl)C 5-8 Cycloalkanes and the like.
[0146] Dihydroxyarenes include hydroquinone, resorcinol, and biphenol.
[0147] Aromatic aliphatic diols include di(hydroxy C) such as 1,4-benzenedimethanol and 1,3-benzenedimethanol. 1-4 Alkyl)C 6-10 Arene, etc.
[0148] Bisphenols include bis(hydroxyphenyl) C such as bisphenol A. 1-10 Alkanes and the like.
[0149] These diol components can be used alone or in combination of two or more. Among these diol components, C 2-6 Alkanediols are preferred, C 2-5 Alkanediols are more preferred, C 3-5 Alkanediols are more preferred.
[0150] The dicarboxylic acid component includes an aliphatic dicarboxylic acid, an alicyclic dicarboxylic acid, an aromatic carboxylic acid, and derivatives of these dicarboxylic acids.
[0151] Examples of aliphatic carboxylic acids include alkane carboxylic acids. Examples of alkane carboxylic acids include C carboxylic acids such as adipic acid, pimelic acid, suberic acid, azelaic acid, and sebacic acid. 2-20 Alkane-dicarboxylic acids and the like.
[0152] Examples of alicyclic dicarboxylic acids include cycloalkane dicarboxylic acids, di- or tricycloalkane dicarboxylic acids, etc. Examples of cycloalkane dicarboxylic acids include C cyclohexane dicarboxylic acid, etc. 5-10 Examples of the di- or tricycloalkane dicarboxylic acid include decalin dicarboxylic acid, norbornane dicarboxylic acid, and adamantane dicarboxylic acid.
[0153] Examples of aromatic dicarboxylic acids include arene dicarboxylic acids, biphenyl dicarboxylic acids, diphenyl alkane dicarboxylic acids, diphenyl ketone dicarboxylic acids, diphenyl ether dicarboxylic acids, etc. Examples of arene dicarboxylic acids include C 111, ... 6-14 Examples of the diphenyl dicarboxylic acids include 2,2'-biphenyl dicarboxylic acid, and examples of the diphenyl alkane dicarboxylic acids include 4,4'-diphenylmethane dicarboxylic acid and 2,2-di(4-carboxyphenyl)hexafluoropropane dicarboxylic acid. 1-10 Examples of the diphenyl ketone dicarboxylic acid include 4,4'-diphenyl ketone dicarboxylic acid, and examples of the diphenyl ether dicarboxylic acid include 4,4'-diphenyl ether dicarboxylic acid.
[0154] Examples of the derivatives of dicarboxylic acids include dicarboxylic acid halides such as dicarboxylic acid chlorides; dicarboxylic acid anhydrides; and lower alkyl esters such as methyl esters and ethyl esters. The lower alkyl esters are C1-4 Alkyl esters are preferred, C 1-2 Alkyl esters are particularly preferred.
[0155] These dicarboxylic acid components can be used alone or in combination of two or more. Among these dicarboxylic acids, cycloalkane-dicarboxylic acids such as 1,4-cyclohexanedicarboxylic acid; arene-dicarboxylic acids such as terephthalic acid, isophthalic acid, and naphthalenecarboxylic acid are preferred, and C 6-10 Arene-dicarboxylic acids are particularly preferred.
[0156] Among these polyester resins, polyalkylene arylate resins such as polyalkylene terephthalate resins and polyalkylene naphthalate resins are preferred from the standpoint of mechanical properties and heat resistance.
[0157] The polyalkylene arylate resin is preferably a polyalkylene arylate resin having an alkylene arylate unit (especially, C such as ethylene terephthalate, butylene terephthalate, and ethylene-2,6-naphthalate). 2-6 Examples of the copolymerizable monomers constituting the copolyester include homopolyesters of 100% by mole or more (especially 100% by mole or more) of alkylene arylate units, and copolyesters having an alkylene arylate unit content of 80 mol % or more (particularly 90 mol % or more). In addition to the above-mentioned dicarboxylic acid component and diol component, examples of the copolymerizable monomers constituting the copolyester include hydroxycarboxylic acids such as hydroxybenzoic acid and lactones such as caprolactone. Of these copolymerizable monomers, dicarboxylic acid components such as isophthalic acid are commonly used. Examples of the polyalkylene arylate resin include polyC such as polyethylene terephthalate resin, polybutylene terephthalate resin, and polyethylene naphthalate resin. 2-4 Alkylene naphthalate resins are preferred.
[0158] Representative polyalkylene arylate resins include poly(C) such as polyethylene terephthalate, polytrimethylene terephthalate, polybutylene terephthalate, and polyethylene naphthalate. 2-10 Alkylene C 8-16Arylate; Poly-C such as poly-1,4-cyclohexanedimethylene terephthalate 5-10 Cycloalkane-diC 1-4 Alkylene C 8-16 Examples include arylates.
[0159] These polyalkylene arylate resins can be used alone or in combination of two or more. Among these, polyC such as polyethylene terephthalate, polybutylene terephthalate, and polyethylene naphthalate are preferred. 2-6 Alkylene C 8-16 Arylate is preferred, and poly(C) such as polybutylene terephthalate. 3-5 Alkylene C 8-12 The arylates are particularly preferred.
[0160] These polyester resins may be crystalline like polyalkylene arylate resins, may be amorphous like polyarylate resins, or may be transparent polyester resins (amorphous transparent polyester resins). The crystallinity of the polyester resins can also be adjusted by the above-mentioned copolymerization components, and the crystallinity may be adjusted by using, for example, asymmetric aliphatic diol components such as propylene glycol and 1,3-butanediol; asymmetric aromatic dicarboxylic acid components such as phthalic acid and isophthalic acid.
[0161] The density of polyester resins is 0.95 to 1.8 g / cm according to ISO 1183. 3 In view of excellent mechanical properties of the resin composition, for example, 1 to 1.75 g / cm 3 ), preferably 1 to 1.7 g / cm 3 , and more preferably 1.1 to 1.5 g / cm 3 , more preferably 1.2 to 1.4 g / cm 3 It is.
[0162] The melt volume flow rate (MVR) of polyester resins is, for example, 5 to 100 cm according to ISO 1133 (250°C, 2.16 kg load). 3 / 10 minutes, preferably 10-50cm 3 / 10 minutes, more preferably 15 to 40 cm 3 / 10 minutes, preferably 20-30cm 3 If the MVR is too small, the melt moldability of the resin composition may decrease, whereas if the MVR is too large, the mechanical properties of the resin composition may decrease.
[0163] The weight average molecular weight of the polyester resin can be selected from the range of about 3,000 to 1,000,000, based on an evaluation method using gel permeation chromatography with polystyrene as the standard, and is, for example, 5,000 to 800,000, preferably 8,000 to 600,000, further preferably 10,000 to 500,000, and further preferably 30,000 to 500,000.
[0164] The glass transition temperature (Tg) of the polyester resin is, for example, 30 to 350°C, preferably 40 to 300°C, further preferably 50 to 250°C, and further preferably 60 to 200°C.
[0165] (Polyamide resin) The polyamide-based resin may be formed of at least one selected from the group consisting of an aliphatic monomer component, an alicyclic monomer component, and an aromatic monomer component. Among these, it is preferable to contain an aliphatic monomer component, and an aliphatic monomer component is particularly preferable.
[0166] In the present specification and claims, a monomer component having a carboxyl group such as a dicarboxylic acid described later may be an acid halide such as an acid chloride, or an amide-forming derivative such as an acid anhydride.
[0167] Examples of the aliphatic monomer component include an aliphatic diamine component, an aliphatic dicarboxylic acid component, an aliphatic aminocarboxylic acid component, and a lactam component.
[0168] Examples of the aliphatic diamine component include linear or branched C diamines such as tetramethylenediamine, hexamethylenediamine, 2-methylpentamethylenediamine, nonamethylenediamine, 2-methyloctamethylenediamine, trimethylhexamethylenediamine, decamethylenediamine, and dodecamethylenediamine. 2-20 Among these, linear or branched C 4-16 Alkylenediamines are preferred, linear or branched C 6-12 Alkylene diamines are particularly preferred.
[0169] Examples of the aliphatic dicarboxylic acid component include saturated aliphatic dicarboxylic acids (straight-chain or branched-chain alkane dicarboxylic acids) and unsaturated aliphatic dicarboxylic acids.
[0170] The linear or branched alkanedicarboxylic acids include linear or branched C alkanedicarboxylic acids such as malonic acid, succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, and 1,10-decanedicarboxylic acid. 1-20 Among these, linear or branched C 2-16 Alkane-dicarboxylic acids are preferred, and linear or branched C alkane-dicarboxylic acids such as adipic acid, sebacic acid, 1,10-decanedicarboxylic acid, etc. 4-12 Alkane-dicarboxylic acids are particularly preferred.
[0171] Unsaturated aliphatic dicarboxylic acids include C 2 O such as maleic acid, fumaric acid, and itaconic acid. 2-10 Alkene-dicarboxylic acids and the like.
[0172] The aliphatic amino carboxylic acid component is amino C such as 6-aminohexanoic acid, 11-aminoundecanoic acid, and 12-aminododecanoic acid. 2-20 Among these, amino C 3-16 Alkyl-carboxylic acids are preferred, amino C 5-11 Alkyl-carboxylic acids are particularly preferred.
[0173] The lactam component may be a lactam corresponding to the aliphatic aminocarboxylic acid, and examples thereof include lactams having 4 to 13 membered rings such as ε-caprolactam, ω-laurolactam, etc. Among these, lactams having 7 to 13 membered rings are preferred.
[0174] The alicyclic monomer component may have an alicyclic skeleton (or an aliphatic hydrocarbon ring skeleton), and examples thereof include an alicyclic diamine component, an alicyclic dicarboxylic acid component, and an alicyclic aminocarboxylic acid component.
[0175] Examples of the alicyclic diamine component include diaminocycloalkanes, bis(aminoalkyl)cycloalkanes, and bis(aminocyclohexyl)alkanes.
[0176] Examples of diaminocycloalkanes include diamino C such as diaminocyclohexane. 5-10 Cycloalkanes and the like.
[0177] Bis(aminoalkyl)cycloalkanes include bis(amino C) such as bis(aminomethyl)cyclohexane. 1-4 Alkyl)C 5-10 Cycloalkanes and the like.
[0178] Bis(aminocyclohexyl)alkanes include bis(aminocyclohexyl)C such as bis(4-aminocyclohexyl)methane and 2,2-bis(4-aminocyclohexyl)propane. 1-6 Alkanes; bis(amino-mono to tri-C, such as bis(4-amino-3-methylcyclohexyl)methane, bis(4-amino-3,5-dimethylcyclohexyl)methane, and 2,2-bis(4-amino-3-methylcyclohexyl)propane 1-6 Alkyl-C 5-10 Cycloalkyl)C 1-6 Alkanes and the like.
[0179] Examples of the alicyclic dicarboxylic acid component include cycloalkane dicarboxylic acids, crosslinked cyclic cycloalkane dicarboxylic acids, cycloalkene dicarboxylic acids, and crosslinked cyclic cycloalkene dicarboxylic acids.
[0180] Cycloalkanedicarboxylic acids include C 1,4-cyclohexanedicarboxylic acid, etc. 5-10 Cycloalkane-dicarboxylic acids and the like.
[0181] Examples of the bridged cyclic cycloalkanedicarboxylic acid include bi- or tricycloalkanedicarboxylic acids such as decalindicarboxylic acid, norbornanedicarboxylic acid, adamantanedicarboxylic acid, and tricyclodecanedicarboxylic acid.
[0182] Examples of cycloalkene dicarboxylic acids include C cyclohexene dicarboxylic acid. 5-10 Cycloalkene-dicarboxylic acids and the like.
[0183] Examples of the bridged cyclic cycloalkene dicarboxylic acid include bi- or tricycloalkene dicarboxylic acids such as norbornene dicarboxylic acid.
[0184] Examples of the alicyclic amino carboxylic acid component include aminocycloalkane carboxylic acids, and specifically, amino C such as aminocyclohexane carboxylic acid. 5-10 Cycloalkane-carboxylic acids and the like.
[0185] The aromatic monomer component may have an aromatic ring skeleton, and examples thereof include aromatic (or aromatic aliphatic) diamine components, aromatic (or aromatic aliphatic) dicarboxylic acid components, and aromatic (or aromatic aliphatic) aminocarboxylic acid components.
[0186] Examples of the aromatic (or aromatic aliphatic) diamine component include diaminoarenes and bis(aminoalkyl)arenes. Examples of the diaminoarenes include diamino C such as m-phenylenediamine, p-phenylenediamine, and m-xylylenediamine. 6-14 Examples of bis(aminoalkyl)arenes include bis(amino C 1-4 alkyl arenes and the like.
[0187] Examples of the aromatic (or araliphatic) dicarboxylic acid component include benzene dicarboxylic acids, alkylbenzene dicarboxylic acids, polycyclic arene dicarboxylic acids, diarylalkane dicarboxylic acids, diaryl ketone dicarboxylic acids, diaryl ether dicarboxylic acids, diaryl sulfide dicarboxylic acids, diaryl sulfone dicarboxylic acids, and the like.
[0188] Examples of benzene dicarboxylic acids include phthalic acid, isophthalic acid, and terephthalic acid. Examples of alkyl benzene dicarboxylic acids include C 4-methylisophthalic acid and 5-methylisophthalic acid. 1-4 Alkyl-benzene dicarboxylic acids and the like.
[0189] Examples of the polycyclic arene dicarboxylic acids include condensed polycyclic arene dicarboxylic acids and ring-assembled arene dicarboxylic acids.
[0190] The condensed polycyclic arene dicarboxylic acids include naphthalene dicarboxylic acids such as 1,2-naphthalene dicarboxylic acid, 1,4-naphthalene dicarboxylic acid, 1,5-naphthalene dicarboxylic acid, 1,8-naphthalene dicarboxylic acid, 2,3-naphthalene dicarboxylic acid, 2,6-naphthalene dicarboxylic acid, and 2,7-naphthalene dicarboxylic acid; anthracene dicarboxylic acid; and condensed polycyclic C such as phenanthrene dicarboxylic acid. 10-24 arene-dicarboxylic acids, preferably fused polycyclic C 10-14 arene-dicarboxylic acids.
[0191] The ring-assembled arene dicarboxylic acids include biC such as 2,2'-biphenyldicarboxylic acid, 3,3'-biphenyldicarboxylic acid, and 4,4'-biphenyldicarboxylic acid. 6-10 arene-dicarboxylic acids.
[0192] Diarylalkanedicarboxylic acids include di-C such as 4,4'-diphenylmethanedicarboxylic acid. 6-10 Aryl C 1-6 Alkane-dicarboxylic acids and the like.
[0193] Examples of diaryl ketone dicarboxylic acids include di(C 6-10 aryl) ketone-dicarboxylic acid and the like.
[0194] Diaryl ether dicarboxylic acids include di(C 6-10 aryl) ether-dicarboxylic acids.
[0195] Diaryl sulfide dicarboxylic acids include di(C) such as 4,4'-diphenyl sulfide dicarboxylic acid. 6-10 aryl)sulfide-dicarboxylic acid and the like.
[0196] Diarylsulfone dicarboxylic acids include di(C) such as 4,4'-diphenylsulfone dicarboxylic acid. 6-10 aryl)sulfone-dicarboxylic acids.
[0197] Examples of the aromatic amino carboxylic acid component include amino arene carboxylic acids. Examples of the amino arene carboxylic acids include amino C such as amino benzoic acid. 6-12 arene-carboxylic acids.
[0198] The polyamide resin can be formed by using these monomer components alone or in combination of two or more kinds, and may be formed, for example, by polymerization of a diamine component and a dicarboxylic acid component, polymerization of an aminocarboxylic acid component and / or a lactam component, polymerization of a diamine component and a dicarboxylic acid component with an aminocarboxylic acid component and / or a lactam component, etc. In addition, the polyamide resin may be a homopolyamide formed of a single monomer component (a single diamine component and a dicarboxylic acid component, a single aminocarboxylic acid component, or a single lactam component), or may be a copolyamide in which a plurality of monomer components are copolymerized. Representative polyamide resins include aliphatic polyamide resins, alicyclic polyamide resins, and aromatic polyamide resins. Of these, aliphatic polyamide resins are preferred.
[0199] The aliphatic polyamide resin may be formed of aliphatic monomer units derived from aliphatic monomer components. Examples of the aliphatic polyamide resin include homopolyamides of aliphatic diamine components and aliphatic dicarboxylic acid components, such as polyamide 46, polyamide 66, polyamide 610, and polyamide 612; homopolyamides of aliphatic aminocarboxylic acid components and / or corresponding lactam components, such as polyamide 6, polyamide 11, and polyamide 12; and copolymers (copolyamides) of multiple aliphatic monomer components, such as copolyamide 6 / 66, copolyamide 6 / 11, and copolyamide 66 / 12.
[0200] In this specification and claims, " / " in copolyamide means that the copolyamide is formed from the monomers (units) before and after it as copolymerization components (copolymerization units). In other words, copolyamide 6 / 66 means that it is a copolymer having units that form polyamide 6 and units that form polyamide 66.
[0201] The aliphatic polyamide resin is preferably an aliphatic polyamide resin containing an aliphatic monomer component having an alkylene group having a carbon number of, for example, 4 to 12, preferably 6 to 11, and more preferably 6 to 9. Representative preferred aliphatic polyamide resins include homopolyamides of an aliphatic diamine component and an aliphatic dicarboxylic acid component, such as polyamide 46, polyamide 66, polyamide 610, and polyamide 612; and homopolyamides of an aliphatic aminocarboxylic acid component, such as polyamide 6, and / or the corresponding lactam component.
[0202] The density of polyamide resins is 0.95 to 1.8 g / cm according to ISO 1183. 3 In view of the excellent mechanical properties of the resin composition, for example, 1 to 1.7 g / cm 3 ), preferably 1 to 1.5 g / cm 3 , and more preferably 1.05 to 1.3 g / cm 3 , more preferably 1.1 to 1.2 g / cm 3 It is.
[0203] The melt volume flow rate (MVR) of polyamide resins is, for example, 10 to 400 cm according to ISO 1133 (275°C, 5 kg load). 3 / 10 minutes, preferably 50-350cm 3 / 10 minutes, more preferably 100 to 300 cm 3 / 10 minutes, preferably 150-250cm 3 If the MVR is too small, the melt moldability of the resin composition may decrease, whereas if the MVR is too large, the mechanical properties of the resin composition may decrease.
[0204] The number average molecular weight Mn of the polyamide resin can be selected from the range of about 7,000 to 1,000,000, for example, 10,000 to 750,000, preferably 20,000 to 500,000, further preferably 30,000 to 500,000, and still more preferably 50,000 to 500,000, based on an evaluation method using gel permeation chromatography with polystyrene as the standard.
[0205] (Ratio of granules) The proportion of the granules can be selected from the range of about 1 to 100 parts by mass relative to 100 parts by mass of the resin, and is preferably 3 to 50 parts by mass, 5 to 30 parts by mass, 10 to 20 parts by mass, 13 to 18 parts by mass, 14 to 17 parts by mass, and most preferably 15 to 16 parts by mass in the following stepwise manner. If the proportion of the granules is too small, it may be difficult to uniformly disperse the plant-derived fibrous filler (A) in the resin, and conversely, if it is too large, the moldability of the resin composition may decrease.
[0206] (Plant-derived fibrous filler) The resin composition of the present disclosure may further contain a second plant-derived fibrous filler in addition to the plant-derived fibrous filler (A) (first plant-derived fibrous filler) contained in the granules. The second fibrous filler, including preferred embodiments, can be selected from the fibrous fillers exemplified as the plant-derived fibrous filler (A) contained in the granules.
[0207] The proportion of the fibrous filler derived from the second plant may be 100 parts by mass or less, for example, 50 parts by mass or less, preferably 10 parts by mass or less, even more preferably 5 parts by mass or less, and more preferably 2 parts by mass or less, for example, 0.1 to 3 parts by mass, relative to 100 parts by mass of the resin.
[0208] In the resin composition of the present disclosure, the granules preferably contain a plant-derived fibrous filler because the plant-derived fibrous filler can be easily uniformly dispersed in the resin composition. Therefore, the resin composition of the present disclosure preferably does not substantially contain, and particularly preferably does not contain, a second plant-derived fibrous filler.
[0209] (Additives) The resin composition of the present disclosure may further contain conventional additives that are blended into resins such as thermoplastic resins. Examples of the additives include coupling agents such as silane coupling agents, softeners, crosslinking agents, crosslinking assistants, fillers or reinforcing agents, plasticizers, anti-aging or antioxidants (such as aromatic amine-based and benzimidazole-based anti-aging agents), colorants such as dyes and pigments, stabilizers (such as ultraviolet absorbers, light resistance stabilizers, and heat stabilizers), release agents, lubricants, flame retardants (such as phosphorus-based flame retardants, halogen-based flame retardants, and inorganic flame retardants), vibration-damping agents, flame retardant assistants, antistatic agents, conductive agents, dispersants, flow regulators, leveling agents, lubricants, defoamers, surface modifiers, stress reducing agents, adhesives, pressure sensitive adhesives, adhesion improvers, tackifiers, nucleating agents, crystallization accelerators, antibacterial agents, and preservatives. These additives can be used alone or in combination of two or more.
[0210] The total proportion of the additives may be 1000 parts by mass or less relative to 100 parts by mass of the resin, for example, 0.01 to 100 parts by mass, preferably 0.1 to 50 parts by mass, more preferably 0.5 to 30 parts by mass, and even more preferably 1 to 20 parts by mass.
[0211] (Characteristics of resin composition) The resin composition of the present disclosure has excellent mechanical properties because the fibrous filler (A) such as cellulose fibers is uniformly dispersed in the resin composition.
[0212] The flexural strength of the resin composition of the present disclosure may be, for example, 10 MPa or more, for example, 10 to 300 MPa, preferably 20 to 200 MPa, and more preferably 30 to 150 MPa.
[0213] When the resin is a polyolefin resin, the resin composition of the present disclosure may have a flexural strength of, for example, 10 to 100 MPa, preferably 20 to 80 MPa, further preferably 22 to 50 MPa, more preferably 25 to 40 MPa, and most preferably 30 to 35 MPa.
[0214] When the resin is a polyacetal resin, the resin composition of the present disclosure may have a flexural strength of, for example, 30 to 300 MPa, preferably 50 to 200 MPa, further preferably 70 to 150 MPa, more preferably 80 to 100 MPa, and most preferably 85 to 95 MPa.
[0215] When the resin is a polyester-based resin, the resin composition of the present disclosure may have a flexural strength of, for example, 30 to 300 MPa, preferably 50 to 200 MPa, further preferably 70 to 150 MPa, more preferably 80 to 120 MPa, and most preferably 90 to 100 MPa.
[0216] When the resin is a polyamide-based resin, the resin composition of the present disclosure may have a flexural strength of, for example, 30 to 300 MPa, preferably 50 to 250 MPa, further preferably 70 to 200 MPa, more preferably 100 to 150 MPa, and most preferably 120 to 130 MPa.
[0217] The resin composition of the present disclosure may have a flexural modulus of 1000 MPa or more, for example, 1000 to 10000 MPa, preferably 1300 to 8000 MPa, and more preferably 1500 to 5000 MPa.
[0218] When the resin is a polyolefin resin, the resin composition of the present disclosure has a flexural modulus of, for example, 1000 to 3000 MPa, preferably 1200 to 2500 MPa, further preferably 1300 to 2000 MPa, further preferably 1400 to 1800 MPa, and most preferably 1500 to 1700 MPa.
[0219] When the resin is a polyacetal resin, the resin composition of the present disclosure has a flexural modulus of, for example, 2000 to 8000 MPa, preferably 2500 to 5000 MPa, further preferably 3000 to 4500 MPa, further preferably 3500 to 4000 MPa, and most preferably 3700 to 3900 MPa.
[0220] When the resin is a polyester resin, the resin composition of the present disclosure has a flexural modulus of, for example, 1500 to 8000 MPa, preferably 2000 to 5000 MPa, further preferably 2500 to 4000 MPa, further preferably 3000 to 3800 MPa, and most preferably 3400 to 3600 MPa.
[0221] When the resin is a polyamide resin, the resin composition of the present disclosure has a flexural modulus of, for example, 2000 to 8000 MPa, preferably 3000 to 5000 MPa, further preferably 3500 to 4500 MPa, further preferably 3800 to 4200 MPa, and most preferably 3900 to 4100 MPa.
[0222] In the present specification and claims, the flexural strength and flexural modulus of a resin composition can be measured in accordance with ISO 178. The flexural strength and flexural modulus are measured for a resin composition that does not contain a reinforcing agent or a filler.
[0223] The shape of the resin composition of the present disclosure is not particularly limited, and may be in the form of pellets or the like.
[0224] (Method of producing resin composition) The resin composition of the present disclosure can be produced by a method including a resin kneading step of kneading granules and resin. In the resin kneading step, the method of kneading granules and resin may be a conventional kneading method depending on the type of resin. Examples of the kneading method include a method of kneading a thermoplastic resin, granules, and other components as necessary by a conventional method such as dry mixing or melt kneading. Among these kneading methods, melt kneading is preferred.
[0225] In the case of melt kneading, the kneading temperature may be equal to or higher than the melting point (or melting temperature) of the organic material (B), for example, 150 to 300°C, preferably 170 to 280°C, and more preferably 180 to 250°C.
[0226] When the thermoplastic resin is a polyolefin resin, the kneading temperature is, for example, 170 to 250°C, preferably 180 to 230°C, and more preferably 190 to 210°C.
[0227] When the thermoplastic resin is a polyacetal resin, the kneading temperature is, for example, 170 to 250°C, preferably 180 to 230°C, and more preferably 190 to 210°C.
[0228] When the thermoplastic resin is a polyester resin, the kneading temperature is, for example, 180 to 280°C, preferably 200 to 250°C, and more preferably 220 to 240°C.
[0229] When the thermoplastic resin is a polyamide resin, the kneading temperature is, for example, 180 to 280°C, preferably 200 to 250°C, and more preferably 220 to 240°C.
[0230] As a method for melt kneading, a conventional method can be used, and it may be a method using an extrusion kneader such as a twin-screw extrusion kneader. The screw rotation speed is, for example, 10 to 1000 rpm, preferably 50 to 300 rpm, and more preferably 100 to 200 rpm.
[0231] (Molded body) The molded article of the present disclosure can be produced by molding the resin composition by a conventional molding method. Conventional molding methods include compression molding, injection molding, injection compression molding, extrusion molding, transfer molding, blow molding, pressure molding, and casting molding. When the resin is a thermoplastic resin, the resin composition of the present disclosure has excellent melt fluidity, so among these molding methods, molding methods that require high melt fluidity, such as injection molding, injection compression molding, and extrusion molding, are preferred, and injection molding is particularly preferred.
[0232] In the injection molding method, the cylinder temperature is, for example, 150 to 300° C., preferably 180 to 280° C., and more preferably 180 to 260° C. If the cylinder temperature is too low, moldability may decrease, and conversely, if it is too high, the mechanical properties of the molded article may decrease.
[0233] When the thermoplastic resin is a polyolefin resin, the cylinder temperature is, for example, 150 to 250°C, preferably 180 to 230°C, and more preferably 190 to 210°C.
[0234] When the thermoplastic resin is a polyacetal resin, the cylinder temperature is, for example, 150 to 250°C, preferably 180 to 230°C, and more preferably 200 to 220°C.
[0235] When the thermoplastic resin is a polyester resin, the cylinder temperature is, for example, 150 to 300°C, preferably 220 to 280°C, and more preferably 240 to 260°C.
[0236] When the thermoplastic resin is a polyamide resin, the cylinder temperature is, for example, 150 to 300°C, preferably 220 to 280°C, and more preferably 240 to 260°C.
[0237] The injection pressure is, for example, 10 to 100 MPa, preferably 20 to 80 MPa, and more preferably 40 to 60 MPa.
[0238] The mold temperature is, for example, 10 to 130° C., preferably 15 to 120° C., and more preferably 20 to 100° C. If the mold temperature is too low, the productivity of the molded article may decrease, whereas if it is too high, the mechanical properties of the molded article may decrease.
[0239] When the thermoplastic resin is a polyolefin resin, the mold temperature is, for example, 10 to 100°C, preferably 15 to 50°C, and more preferably 20 to 40°C.
[0240] When the thermoplastic resin is a polyacetal resin, the mold temperature is, for example, 10 to 100°C, preferably 20 to 70°C, and more preferably 30 to 50°C.
[0241] When the thermoplastic resin is a polyester resin, the mold temperature is, for example, 30 to 120°C, preferably 50 to 90°C, and more preferably 60 to 80°C.
[0242] When the thermoplastic resin is a polyamide resin, the mold temperature is, for example, 30 to 130°C, preferably 60 to 100°C, and more preferably 70 to 90°C.
[0243] The shape of the molded article of the present disclosure is not particularly limited and can be selected according to the application, and examples thereof include one-dimensional structures such as linear or thread-like structures, two-dimensional structures such as film-like, sheet-like, and plate-like structures, and three-dimensional structures such as block-like, rod-like, tubular, hollow, etc. In particular, since the resin composition of the present disclosure can be used to produce molded articles with high productivity by injection molding, even three-dimensional structures can be produced with high productivity.
[0244] [Rubber composition] The rubber composition of the present disclosure includes the granules and rubber. The granules are granular and have a specific bulk density, and therefore are easy to handle. For example, when the granules and rubber are kneaded to prepare a rubber composition, the granules can be smoothly fed into a kneader, and the fibrous filler (A) contained in the granules can be prevented from agglomerating even when kneaded with rubber. Therefore, the fibrous filler (A) can be uniformly dispersed in the rubber composition, and the mechanical properties of the rubber composition can be improved.
[0245] (Rubber) The rubber contained in the resin composition is an unvulcanized rubber component. The rubber is not particularly limited, and conventional rubbers can be used. Conventional rubbers include diene rubbers, olefin rubbers, acrylic rubbers (ACM, ANM), butyl rubbers (IIR), epichlorohydrin rubbers (CO), polysulfide rubbers (OT, EOT), urethane rubbers (U), silicone rubbers (Q), fluororubbers (FFKM, FKM), and sulfur-containing rubbers. These rubbers can be used alone or in combination of two or more. Among these rubbers, diene rubbers and / or olefin rubbers are preferred because of their large effect of improving the dispersibility of the fibrous filler (A).
[0246] Examples of diene rubbers include natural rubber (NR), epoxidized natural rubber, polybutadiene (e.g., butadiene rubber (BR), 1,2-polybutadiene (VBR), etc.), isoprene rubber (IR), chloroprene rubber (CR), acrylonitrile-butadiene rubber (NBR), styrene-butadiene rubber (SBR), etc. These diene rubbers may be hydrogenated rubbers (e.g., hydrogenated BR, hydrogenated NBR, hydrogenated SBR, etc.). These diene rubbers may be used alone or in combination of two or more.
[0247] Examples of olefin-based rubbers include ethylene-propylene rubber (EPM), ethylene-propylene-diene rubber (EPDM), ethylene-butene rubber, ethylene-1-butene-diene rubber, propylene-1-butene-diene rubber, polyisobutylene rubber, ethylene-vinyl acetate rubber, maleic acid modified ethylene-propylene rubber (M-EPM), chlorosulfonated polyethylene (CSM), chlorinated polyethylene (CM), maleic acid modified chlorinated polyethylene (M-CM), etc. Examples of diene units (non-conjugated diene units) contained in olefin-based rubbers include units derived from dicyclopentadiene, 1,4-hexadiene, cyclooctadiene, methylenenorbornene, and ethylidenenorbornene. These olefin-based rubbers can be used alone or in combination of two or more.
[0248] The copolymer rubber may be a random or block copolymer, and the block copolymer includes copolymers having an AB type, ABA type, tapered type, or radial teleblock type structure.
[0249] Of these, diene rubbers and / or olefin rubbers are preferred, and at least one selected from the group consisting of SBR, EPM and EPDM is particularly preferred.
[0250] Among them, diene rubbers are preferred because they can highly improve the hardness and tear strength of the vulcanizate of the rubber composition.Furthermore, among the diene rubbers, diene rubbers having an aromatic skeleton or aromatic ring, such as SBR, are particularly preferred because they have a large effect of improving the dispersibility of the fibrous filler (A).
[0251] The proportion of the diene rubber in the rubber may be 50% by mass or more, preferably 80% by mass or more, further preferably 90% by mass or more, and most preferably 100% by mass.
[0252] (Ratio of granules) The proportion of the granules can be selected from the range of about 1 to 100 parts by mass relative to 100 parts by mass of rubber, and is preferably 3 to 50 parts by mass, 5 to 40 parts by mass, 5.5 to 30 parts by mass, 6 to 20 parts by mass, 6 to 15 parts by mass, 6.5 to 12 parts by mass, and most preferably 7 to 10 parts by mass. If the proportion of the granules is too small, it may be difficult to uniformly disperse the plant-derived fibrous filler (A) in the rubber, and conversely, if it is too large, the moldability of the rubber composition may decrease.
[0253] (Plant-derived fibrous filler) The rubber composition of the present disclosure may further contain a third plant-derived fibrous filler in addition to the plant-derived fibrous filler (A) (first plant-derived fibrous filler) contained in the granules. The third fibrous filler, including preferred embodiments, can be selected from the fibrous fillers exemplified as the plant-derived fibrous filler (A) contained in the granules.
[0254] The proportion of the third plant-derived fibrous filler relative to 100 parts by mass of rubber may be 100 parts by mass or less, for example, 10 parts by mass or less, preferably 5 parts by mass or less, even more preferably 3 parts by mass or less, more preferably 2 parts by mass or less, and most preferably 1 part by mass or less, for example, 0.1 to 2 parts by mass.
[0255] In the rubber composition of the present disclosure, the granules preferably contain a plant-derived fibrous filler because the plant-derived fibrous filler can be easily uniformly dispersed in the rubber composition. Therefore, the rubber composition of the present disclosure preferably does not substantially contain, and particularly preferably does not contain, a third plant-derived fibrous filler.
[0256] (Additives) The rubber composition of the present disclosure may further contain conventional additives that are compounded with rubber. Examples of the additives include vulcanizing agents (sulfur-based vulcanizing agents such as sulfur, organic peroxides, etc.), vulcanization aids, fillers or reinforcing agents (carbon black, silica, short fibers, etc.), coupling agents such as silane coupling agents, softeners, plasticizers, antiaging or oxidation inhibitors (aromatic amine-based, benzimidazole-based antiaging agents, etc.), colorants such as dyes and pigments, stabilizers (ultraviolet absorbers, light resistance stabilizers, heat stabilizers, etc.), release agents, lubricants, flame retardants (phosphorus-based flame retardants, halogen-based flame retardants, inorganic flame retardants, etc.), vibration-damping agents, flame retardant assistants, antistatic agents, conductive agents, dispersants, flow regulators, leveling agents, lubricants, defoamers, surface modifiers, stress reducers, adhesives, pressure-sensitive adhesives, adhesion improvers, tackifiers, nucleating agents, crystallization accelerators, antibacterial agents, and preservatives. These additives may be used alone or in combination of two or more.
[0257] The total proportion of the additives may be 1000 parts by mass or less per 100 parts by mass of rubber, for example, 0.01 to 100 parts by mass, preferably 0.1 to 50 parts by mass, further preferably 0.5 to 30 parts by mass, and further preferably 1 to 20 parts by mass.
[0258] (Characteristics of rubber composition) The rubber composition of the present disclosure has excellent mechanical properties because the fibrous filler (A) such as cellulose fibers is uniformly dispersed in the rubber composition.
[0259] The vulcanizate (crosslinked product) of the rubber composition of the present disclosure has high hardness. The hardness (type A durometer) of the vulcanizate of the rubber composition of the present disclosure may be 30 or more, for example, 35 to 50, preferably 37 to 45, further preferably 38 to 43, and further preferably 39 to 41.
[0260] In this specification and claims, hardness (type A durometer) can be measured using a durometer (type A) in accordance with ISO 7619-1.
[0261] (Method of manufacturing rubber composition) The rubber composition of the present disclosure can be produced by a method including a rubber kneading step of kneading granules and rubber. In the rubber kneading step, the granules and rubber may be kneaded by a conventional kneading method depending on the type of rubber. Examples of the kneading method include a method of kneading using a roll kneader such as a mixing roller, and a method of kneading using an internal kneader such as a Banbury mixer, an intermix, a kneader, or an extruder (such as a single-screw or twin-screw extruder). Among these kneading methods, the kneading method using an internal kneader is preferred from the viewpoint of facilitating uniform kneading of the fibrous filler (A), and the kneading method using a kneader is particularly preferred.
[0262] The kneading temperature can be appropriately selected depending on the type of rubber, but may be a temperature equal to or higher than the melting point or melting temperature of the organic material (B), for example, 80 to 200°C, preferably 100 to 150°C, further preferably 105 to 140°C, further preferably 110 to 135°C, and most preferably 115 to 130°C.
[0263] The screw rotation speed is, for example, 5 to 500 rpm, preferably 10 to 100 rpm, and more preferably 30 to 50 rpm. The kneading time is, for example, 0.5 to 60 minutes, preferably 1 to 30 minutes, and more preferably 3 to 10 minutes.
[0264] (Molded body) The molded article of the present disclosure can be produced by molding the rubber composition by a conventional molding method. The conventional molding method may be any method that includes a vulcanization step of vulcanizing (or crosslinking) the rubber composition.
[0265] In the vulcanization step, the vulcanization temperature can be selected depending on the type of rubber and is, for example, 100 to 250°C, preferably 130 to 200°C, further preferably 140 to 190°C, and further preferably 145 to 180°C.
[0266] The shape of the molded article of the present disclosure is not particularly limited and can be selected according to the application, and examples thereof include one-dimensional structures such as linear or thread-like structures, two-dimensional structures such as film, sheet, plate, and three-dimensional structures such as block, rod, tube, hollow, etc. In particular, since the rubber composition of the present disclosure can be used to produce molded articles with high productivity by injection molding, even three-dimensional structures can be produced with high productivity. EXAMPLES
[0267] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples. The raw materials, equipment and evaluation methods used in the examples are as follows.
[0268] [Raw materials] (Plant-derived fibrous filler) Cellulose fiber: A sheet of plant-derived pulp (unmodified fiber, average fiber diameter 40 μm, average fiber length 1 mm or more) cut into chips of approximately 4 mm x 4 mm square, with a bulk density of 0.15 g / cm 3 .
[0269] (organic material) BPEF: 9,9-bis[4-(2-hydroxyethoxy)phenyl]fluorene, "BPEF" manufactured by Osaka Gas Chemicals Co., Ltd., molecular weight 438.5, solid at room temperature, powder form, average particle size 3 μm Stearic acid: manufactured by Tokyo Chemical Industry Co., Ltd., molecular weight 284.5, solid at room temperature, powder form, average particle size 2 μm Stearic acid amide: manufactured by Tokyo Chemical Industry Co., Ltd., molecular weight 283.5, solid at room temperature, powder form, average particle size 2 μm BisA-2EO: 4,4'-isopropylidenebis(2-phenoxyethanol), Fujifilm Wako Pure Chemical Industries, molecular weight 316.4, solid at room temperature, powder, average particle size 2 μm PEG200: Polyethylene glycol 200, manufactured by Tokyo Chemical Industry Co., Ltd., average molecular weight 190 to 210, liquid at room temperature.
[0270] (thermoplastic resin) High density polyethylene resin (HDPE): "Novatec HD HJ490" manufactured by Japan Polyethylene Co., Ltd. Polyacetal resin (POM): "Duracon M450-44" manufactured by Polyplastics Co., Ltd. Polybutylene terephthalate resin (PBT): "Novaduran 5010R5" manufactured by Mitsubishi Engineering Plastics Corporation Polyamide 6 resin (PA6): "Unitika Nylon A1030BRL" manufactured by Unitika Ltd.
[0271] (Rubber) SBR: "ESBR 1502" manufactured by ENEOS Material Co., Ltd.
[0272] [Equipment used] Mixer: Kawata Co., Ltd. "Super Mixer SMV-20B" Extrusion granulator: Dalton "Disc Pelleter F-5", die diameter 3 mm Twin screw extruder: Technovel Co., Ltd. "MFU25W-45MG-NH" Injection molding machine: Thermo Fisher Scientific "HAAKE MiniJet Pro" Batch kneader: Technovel Co., Ltd. "MSR-60" Manual hydraulic vacuum heating press: Manufactured by Imoto Manufacturing Co., Ltd.
[0273] [Granulation] In Examples 1 to 6 and Comparative Examples 1 and 2, the cellulose fiber, the organic material, and the water were granulated in an extrusion granulator, and the granulation properties were evaluated according to the following criteria.
[0274] Possible: Granulation was stable and the product solidified into pellets. Unacceptable: The product did not solidify into pellets and could not be granulated.
[0275] [Granule shape] The shapes of the granules obtained in Examples 1 to 6 were evaluated according to the following criteria.
[0276] ○: Close to pellet shape △: Pellet-like, but has many cracks and splinters on the surface.
[0277] [Bulk density] The granules obtained in Examples 1 to 6 and the flocculants obtained in Comparative Examples 4 and 5 were each placed in a 100 mL measuring cylinder in an amount of 100 mL without tapping, the mass of the contents was measured, and the bulk density was calculated according to the following formula.
[0278] Bulk density (g / cm 3 ) = mass of contents (g) / volume (100cm 3 ).
[0279] [Supplyability] In Examples 7 to 15 and Comparative Examples 3 to 12, when preparing the resin compositions, the feedability of the raw materials to the feeder of the twin-screw extruder, which is a kneader, was evaluated according to the following criteria.
[0280] Possible: The raw materials were supplied to the mixer stably. Unacceptable: Bridges occurred and raw materials could not be fed to the kneader.
[0281] [Cohesiveness of resin composition or rubber composition] The presence or absence of aggregates on the surfaces of the resin compositions (kneaded products) obtained in Examples 7 to 15 and Comparative Examples 6, 8, 10, and 12, and the rubber compositions (kneaded products) obtained in Examples 16 to 18 were observed and evaluated according to the following criteria.
[0282] None: No agglomerates were observed on the surface of the kneaded product (details are as follows)
[0283] (Resin: Randomly extracted pellets of kneaded material (approximately 3 mm in diameter and 3 mm in length) Of the 50 pellets, there is one or less that contains aggregates with a diameter of 0.5 mm or more. Rubber: Prepare a press sheet of 75mm x 75mm x 2mm at 150℃ When the press sheet is pressed, there is one or less aggregate with a diameter of 0.5 mm or more.
[0284] Slight: A small amount of agglomerates were observed on the surface of the kneaded product (details are as follows)
[0285] (Resin: Randomly extracted pellets of kneaded material (approximately 3 mm in diameter and 3 mm in length) Of the 50 pellets, 2 or more contain aggregates with a diameter of 0.5 mm or more. 5 pieces or less Rubber: Prepare a press sheet of 75mm x 75mm x 2mm at 150℃ When the press sheet is subjected to the above test, two or more aggregates with a diameter of 0.5 mm or more are found. (5 pieces or less)
[0286] Many aggregates were observed on the surface of the kneaded material (details are as follows)
[0287] (Resin: Randomly extracted pellets of kneaded material (approximately 3 mm in diameter and 3 mm in length) Of the 50 pellets, 6 or more contain aggregates with a diameter of 0.5 mm or more. Rubber: Prepare a press sheet of 75mm x 75mm x 2mm at 150℃ When the press sheet is subjected to the above test, there are six or more aggregates with a diameter of 0.5 mm or more.
[0288] [Flexural strength and flexural modulus] The flexural strength and flexural modulus of the rectangular test pieces obtained in Examples 7 to 15 and Comparative Examples 3 and 6 to 12 were measured in accordance with ISO 178.
[0289] [Durometer hardness] The durometer hardness of the sheet-like test pieces obtained in Examples 16 to 18 and Comparative Example 13 was measured in accordance with ISO 7619-1.
[0290] [Example 1] 100 parts by mass of cellulose fiber, 33.3 parts by mass of BPEF, and 166.7 parts by mass of water were stirred for 10 minutes at a rotation speed of 2000 rpm using a mixer. The resulting mixture was granulated in a non-heated state using an extrusion granulator to produce a wet granule, and the granulation property was evaluated. Next, the obtained wet granule was dried at 100°C for 8 hours using a vacuum dryer to remove moisture, and granule A was obtained. The shape of the obtained granule A was evaluated.
[0291] [Example 2] Granules B were produced in the same manner as in Example 1 except that the ratio of BPEF and water was changed to the ratio shown in Table 1, and the granulation properties and shape of granules B were evaluated.
[0292] [Example 3] Granules C were produced in the same manner as in Example 1 except that the ratio of BPEF and water was changed to the ratio shown in Table 1, and the granulation properties and shape of granules C were evaluated.
[0293] [Example 4] Granule D was produced in the same manner as in Example 1 except for using stearic acid instead of BPEF, and the granulation properties and shape of granule D were evaluated.
[0294] [Example 5] Granule E was produced in the same manner as in Example 1 except that stearic acid amide was used instead of BPEF, and the granulation properties and shape of granule E were evaluated.
[0295] [Example 6] Granule F was produced in the same manner as in Example 1 except for using BisA-2EO instead of BPEF, and the granulation properties and shape of granule F were evaluated.
[0296] [Comparative Example 1] 100 parts by mass of cellulose fiber and 100 parts by mass of water were stirred for 10 minutes at a rotation speed of 2000 rpm using a mixer. The resulting mixture was granulated using an extrusion granulator, but the mixture did not solidify into pellets, and granulation was not possible.
[0297] [Comparative Example 2] 100 parts by mass of cellulose fiber, 33.3 parts by mass of PEG200, and 166.7 parts by mass of water were stirred for 10 minutes at a rotation speed of 2000 rpm using a mixer. The resulting mixture was granulated using an extrusion granulator, but it did not solidify into pellets, and granulation was not possible.
[0298] Table 1 shows the compositions and evaluation results of Examples 1 to 6 and Comparative Examples 1 and 2.
[0299] [Table 1]
[0300] As is clear from Table 1, in Comparative Example 1, which contains only cellulose fiber and water, the product did not solidify and could not be granulated, whereas in Examples 1 to 3, in which BPEF was added in addition to cellulose fiber and water, stable granulation was possible. In addition, when Examples 1 to 3 are compared, in Example 3, in which the amount of BPEF is relatively small, cracks and burrs were noticeable in the granules, whereas in Examples 1 to 2, in which the amount of BPEF is relatively large, there was no problem with the shape of the granules. In addition, in Examples 4 to 6, in which various organic materials were used instead of BPEF, granulation was possible without any problems, as in Examples 1 to 2. On the other hand, in Comparative Example 2, in which PEG200, a comparative material that is a liquid compound, was used instead of BPEF, the product did not solidify and could not be granulated, as in Comparative Example 1.
[0301] [Example 7] 86.7 parts by mass of HDPE and 13.3 parts by mass of the granules A obtained in Example 1 were kneaded using a twin-screw extruder at a temperature of 200°C, a screw rotation speed of 150 rpm, and a discharge rate of about 10 kg / h to prepare a pellet-shaped resin composition, and the feedability and cohesiveness were evaluated. During kneading, HDPE was top-fed using the top feeder of the extruder, and granules A was side-fed using the side feeder of the extruder. The obtained resin composition was injection-molded using an injection molding machine under conditions of a cylinder temperature of 200°C and a mold temperature of 30°C to obtain a rectangular test piece. The bending strength and bending modulus of the obtained test piece were measured.
[0302] [Example 8] 86.7 parts by mass of HDPE, 1.6 parts by mass of BPEF, and 11.7 parts by mass of the granules B obtained in Example 2 were kneaded using a twin-screw extruder at a temperature of 200°C, a screw rotation speed of 150 rpm, and a discharge rate of about 10 kg / h to prepare a pellet-shaped resin composition, and the feedability and cohesiveness were evaluated. During kneading, HDPE and BPEF were top-fed using the top feeder of the extruder, and granules B were side-fed using the side feeder of the extruder. The obtained resin composition was injection-molded using an injection molding machine under conditions of a cylinder temperature of 200°C and a mold temperature of 30°C to obtain a strip-shaped test piece. The bending strength and bending modulus of the obtained test piece were measured.
[0303] [Example 9] 86.7 parts by mass of HDPE, 2.3 parts by mass of BPEF, and 11.0 parts by mass of the granules C obtained in Example 3 were kneaded using a twin-screw extruder at a temperature of 200°C, a screw rotation speed of 150 rpm, and a discharge rate of about 10 kg / h to prepare a pellet-shaped resin composition, and the feedability and cohesiveness were evaluated. During kneading, HDPE and BPEF were top-fed using the top feeder of the extruder, and granules C were side-fed using the side feeder of the extruder. The obtained resin composition was injection-molded using an injection molding machine under conditions of a cylinder temperature of 200°C and a mold temperature of 30°C to obtain a strip-shaped test piece. The bending strength and bending modulus of the obtained test piece were measured.
[0304] [Examples 10 to 12] Strip-shaped test pieces were produced in the same manner as in Example 7, except that granules D to F were used instead of granule A, and the feeding property and cohesiveness were evaluated, and the bending strength and bending modulus of the test pieces were measured.
[0305] [Comparative Example 3] HDPE was mixed in a twin-screw extruder at 200°C, 150 rpm screw speed, and 10 kg / h extrusion rate to prepare pelletized resin, and feedability was evaluated. During mixing, HDPE was top-fed using the top feeder of the extruder. The resulting resin pellets were injection-molded in an injection molding machine at a cylinder temperature of 200°C and a mold temperature of 30°C to obtain rectangular test pieces. The flexural strength and flexural modulus of the resulting test pieces were measured.
[0306] [Comparative Example 4] (Preparation of Cotton-like Body A) A cotton-like material A was obtained in the same manner as in Example 1, except that the material was not granulated in an extrusion granulator but was vacuum dried to remove moisture. The obtained cotton-like material A was cotton-like and had a bulk density of 0.06 g / cm. 3 It was.
[0307] (Preparation of strip-shaped test pieces) Kneading was attempted in the same manner as in Example 7, except for using cotton-like material A instead of granules A. However, due to the low bulk density of the cotton-like material A, there was a problem with feeding it into the kneader, and it was not possible to produce a kneaded product.
[0308] [Comparative Example 5] (Preparation of Cotton-like Body B) 200 g of water was added to 100 g of cellulose fiber and mixed in a household mixer to obtain 300 g of a water-wetted material with a solid content of 33% by mass. 300 g of propylene glycol monomethyl ether acetate and 33.3 g of BPEF were added to the obtained water-wetted material, and after stirring, the water and propylene glycol monomethyl ether acetate were removed under reduced pressure at 80° C., and a cotton-like material B was obtained. The bulk density of the obtained cotton-like material B was 0.05 g / cm. 3 It was.
[0309] (Preparation of strip-shaped test pieces) Kneading was attempted in the same manner as in Example 7, except for using cotton-like material B instead of granules A. However, due to the low bulk density of cotton-like material B, there was a problem with feeding it to the kneader, and it was not possible to produce a kneaded product.
[0310] [Comparative Example 6] 86.7 parts by mass of HDPE, 3.3 parts by mass of BPEF, and 10.0 parts by mass of cellulose fiber were kneaded using a twin-screw extruder at a temperature of 200°C, a screw rotation speed of 150 rpm, and a discharge rate of about 10 kg / h to prepare a pellet-shaped resin composition, and the feedability and cohesiveness were evaluated. During kneading, HDPE and BPEF were top-fed using the top feeder of the extruder, and cellulose fiber was side-fed using the side feeder of the extruder. The obtained resin composition was injection-molded using an injection molding machine under conditions of a cylinder temperature of 200°C and a mold temperature of 30°C to obtain a rectangular test piece. The bending strength and bending modulus of the obtained test piece were measured.
[0311] Table 2 shows the compositions and evaluation results of Examples 7 to 12 and Comparative Examples 3 to 6.
[0312] [Table 2]
[0313] As is clear from Table 2, in Examples 7 to 9 containing BPEF-containing granules and HDPE, the bending strength and bending modulus were improved compared to Comparative Example 3 containing only HDPE. On the other hand, in Comparative Examples 4 and 5, kneading of HDPE with a cotton-like body was attempted, but the bulk density of the cotton-like body was low, so that poor feeding to the kneader occurred and a kneaded product could not be produced. In Comparative Example 6, kneading was performed with HDPE, cellulose fiber, and BPEF, but the dispersibility of the cellulose fiber was insufficient, and many aggregates were observed on the surface of the kneaded product. Perhaps due to these aggregates, the bending strength and bending modulus of Comparative Example 6 were inferior to those of Examples 7 to 9. In addition, when Examples 7 to 9 are compared, in Example 9 using granules with a relatively small amount of BPEF, some aggregates were observed on the surface of the kneaded product. This is thought to be because when the amount of BPEF during the production of the granules becomes relatively small, it is not possible to completely suppress the aggregation of the cellulose fibers during drying. Perhaps due to these aggregates, the bending strength and bending modulus of Example 9 were slightly lower than those of Examples 7 and 8. In addition, Examples 10 to 12, which contained various organic material-containing granules other than BPEF and HDPE, had no problems with feedability to the kneader or surface agglomeration, as did Examples 7 to 8, which used BPEF-containing granules. However, since the skeleton of the organic material used was softer than that of BPEF and did not have a polycyclic aromatic ring, the bending strength and bending modulus of Examples 10 to 12 were inferior to those of Examples 7 to 8.
[0314] [Example 13] 86.7 parts by mass of POM and 13.3 parts by mass of the granule A obtained in Example 1 were kneaded using a twin-screw extruder at a temperature of 200°C, a screw rotation speed of 150 rpm, and a discharge rate of about 10 kg / h to prepare a pellet-shaped resin composition, and the feedability and cohesiveness were evaluated. During kneading, POM was top-fed using the top feeder of the extruder, and granule A was side-fed using the side feeder of the extruder. The obtained resin composition was injection-molded using an injection molding machine under conditions of a cylinder temperature of 210°C and a mold temperature of 40°C to obtain a strip-shaped test piece. The bending strength and bending modulus of the obtained test piece were measured.
[0315] [Example 14] 86.7 parts by mass of PBT and 13.3 parts by mass of the granules A obtained in Example 1 were kneaded using a twin-screw extruder at a temperature of 230°C, a screw rotation speed of 150 rpm, and a discharge rate of about 10 kg / h to prepare a pellet-shaped resin composition, and the feedability and cohesiveness were evaluated. During kneading, PBT was top-fed using the top feeder of the extruder, and granules A was side-fed using the side feeder of the extruder. The obtained resin composition was injection-molded using an injection molding machine under conditions of a cylinder temperature of 250°C and a mold temperature of 70°C to obtain a strip-shaped test piece. The bending strength and bending modulus of the obtained test piece were measured.
[0316] [Example 15] 86.7 parts by mass of PA6 and 13.3 parts by mass of the granules A obtained in Example 1 were kneaded using a twin-screw extruder at a temperature of 230°C, a screw rotation speed of 150 rpm, and a discharge rate of about 10 kg / h to prepare a pellet-shaped resin composition, and the feedability and cohesiveness were evaluated. During kneading, PA6 was top-fed using the top feeder of the extruder, and granules A was side-fed using the side feeder of the extruder. The obtained resin composition was injection-molded using an injection molding machine under conditions of a cylinder temperature of 250°C and a mold temperature of 80°C to obtain a strip-shaped test piece. The bending strength and bending modulus of the obtained test piece were measured.
[0317] [Comparative Example 7] POM was mixed in a twin-screw extruder at a temperature of 200°C, a screw speed of 150 rpm, and a discharge rate of approximately 10 kg / h to prepare pellet-shaped resin, and the feedability was evaluated. During mixing, POM was top-fed using the top feeder of the extruder. The obtained resin pellets were injection-molded using an injection molding machine at a cylinder temperature of 210°C and a mold temperature of 40°C to obtain rectangular test pieces. The flexural strength and flexural modulus of the obtained test pieces were measured.
[0318] [Comparative Example 8] 86.7 parts by mass of POM, 3.3 parts by mass of BPEF, and 10.0 parts by mass of cellulose fiber were kneaded using a twin-screw extruder at a temperature of 200°C, a screw rotation speed of 150 rpm, and a discharge rate of about 10 kg / h to prepare a pellet-shaped resin composition, and the feedability and cohesiveness were evaluated. During kneading, POM and BPEF were top-fed using the top feeder of the extruder, and cellulose fiber was side-fed using the side feeder of the extruder. The obtained resin composition was injection-molded using an injection molding machine under conditions of a cylinder temperature of 210°C and a mold temperature of 40°C to obtain a rectangular test piece. The bending strength and bending modulus of the obtained test piece were measured.
[0319] [Comparative Example 9] PBT was kneaded using a twin-screw extruder at a temperature of 230°C, a screw speed of 150 rpm, and a discharge rate of approximately 10 kg / h to prepare pellet-shaped resin, and the feedability was evaluated. During kneading, PBT was top-fed using the top feeder of the extruder. The obtained resin pellets were injection-molded using an injection molding machine under conditions of a cylinder temperature of 250°C and a mold temperature of 70°C to obtain rectangular test pieces. The flexural strength and flexural modulus of the obtained test pieces were measured.
[0320] [Comparative Example 10] 86.7 parts by mass of PBT, 3.3 parts by mass of BPEF, and 10.0 parts by mass of cellulose fiber were kneaded using a twin-screw extruder at a temperature of 230°C, a screw rotation speed of 150 rpm, and a discharge rate of about 10 kg / h to prepare a pellet-shaped resin composition, and the feedability and cohesiveness were evaluated. During kneading, PBT and BPEF were top-fed using the top feeder of the extruder, and cellulose fiber was side-fed using the side feeder of the extruder. The obtained resin composition was injection-molded using an injection molding machine under conditions of a cylinder temperature of 250°C and a mold temperature of 70°C to obtain a strip-shaped test piece. The bending strength and bending modulus of the obtained test piece were measured.
[0321] [Comparative Example 11] PA6 was kneaded using a twin-screw extruder at a temperature of 230°C, a screw speed of 150 rpm, and a discharge rate of about 10 kg / h to prepare a pellet-shaped resin, and the feedability was evaluated. During kneading, PA6 was top-fed using a top feed. The obtained resin pellets were injection-molded using an injection molding machine under conditions of a cylinder temperature of 250°C and a mold temperature of 80°C to obtain a rectangular test piece. The flexural strength and flexural modulus of the obtained test piece were measured.
[0322] [Comparative Example 12] 86.7 parts by mass of PA6, 3.3 parts by mass of BPEF, and 10.0 parts by mass of cellulose fiber were kneaded using a twin-screw extruder at a temperature of 230°C, a screw rotation speed of 150 rpm, and a discharge rate of about 10 kg / h to prepare a pellet-shaped resin composition, and the feedability and cohesiveness were evaluated. During kneading, PA6 and BPEF were top-fed using the top feeder of the extruder, and cellulose fiber was side-fed using the side feeder of the extruder. The obtained resin composition was injection-molded using an injection molding machine under conditions of a cylinder temperature of 250°C and a mold temperature of 80°C to obtain a strip-shaped test piece. The flexural strength and flexural modulus of the obtained test piece were measured.
[0323] Table 3 shows the compositions and evaluation results of Examples 13 to 15 and Comparative Examples 7 to 12.
[0324] [Table 3]
[0325] As is clear from Table 3, the bending strength and bending modulus were improved in Examples 13, 14, and 15 containing the corresponding resin and granules, compared to Comparative Example 7, Comparative Example 9, and Comparative Example 11 containing only resin. In contrast, in Comparative Examples 8, 10, and 12, kneading was performed with resin, cellulose fiber, and BPEF, but the dispersibility of the cellulose fiber was insufficient, and many aggregates were observed on the surface of the kneaded product. Perhaps due to these aggregates, the bending strength and bending modulus of Comparative Examples 8, 10, and 12 were inferior to those of Examples 13, 14, and 15 containing the corresponding resin and granules.
[0326] [Example 16] 93.3 parts by mass of SBR and 6.7 parts by mass of the granules A obtained in Example 1 were kneaded for 5 minutes at a temperature of 120°C and a screw rotation speed of 40 rpm using a batch kneader to prepare a lump-shaped rubber composition. The obtained rubber composition was pressed for 2 minutes using a manual hydraulic vacuum heating press under the condition of a hot plate temperature of 150°C to obtain a sheet-shaped test piece.
[0327] [Example 17] 93.3 parts by mass of SBR, 0.9 parts by mass of BPEF, and 5.8 parts by mass of the granules B obtained in Example 2 were kneaded for 5 minutes at a temperature of 120°C and a screw rotation speed of 40 rpm using a batch kneader to prepare a lump-shaped rubber composition. The obtained rubber composition was pressed for 2 minutes using a manual hydraulic vacuum heating press under the condition of a hot plate temperature of 150°C to obtain a sheet-shaped test piece.
[0328] [Example 18] 93.3 parts by mass of SBR, 1.2 parts by mass of BPEF, and 5.5 parts by mass of the granules C obtained in Example 3 were kneaded for 5 minutes at a temperature of 120°C and a screw rotation speed of 40 rpm using a batch kneader to prepare a lump-shaped rubber composition. The obtained rubber composition was pressed for 2 minutes using a manual hydraulic vacuum heating press under the condition of a hot plate temperature of 150°C to obtain a sheet-shaped test piece.
[0329] [Comparative Example 13] The SBR was pressed for 2 minutes using a manual hydraulic vacuum heating press at a hot platen temperature of 150° C. to obtain a sheet-like test piece.
[0330] Table 4 shows the compositions and evaluation results of Examples 16 to 18 and Comparative Example 13.
[0331] [Table 4]
[0332] As is clear from Table 4, the hardness was improved in Examples 16 to 18 containing SBR and granules compared to Comparative Example 13 containing only SBR. In addition, when Examples 16 to 18 were compared, the surface aggregates of the kneaded material tended to increase in the order of Examples 16, 17, and 18, in which the amount of BPEF in the granules was smaller. This is thought to be because the smaller the amount of BPEF when preparing the granules, the more insufficient the inhibition of aggregation between cellulose fibers during drying. Perhaps due to these aggregates, the hardness decreased in the order of Examples 16, 17, and 18, in which the amount of BPEF in the granules was smaller. In addition, the rubber composition tended to be more likely to generate aggregates than the resin composition using the same granules (Examples 16 and 7, and Examples 17 and 8). This is thought to be because the batch kneader used for rubber kneading has a smaller shear force than the twin-screw extruder used for resin kneading, making it easier for aggregates to generate. [Industrial Applicability]
[0333] The granules of the present disclosure have excellent dispersibility in resins and rubbers, and can be used as reinforcing agents for resins and rubbers. Resin compositions containing the granules of the present disclosure can be used for resin molded products in various fields [for example, automobile parts, electric and electronic parts, building materials (wall materials, etc.), civil engineering materials, agricultural materials, packaging materials (containers, cushioning materials, etc.), living materials (daily necessities, etc.), optical members, etc.]. Rubber compositions containing the granules of the present disclosure can be used for various industrial members (belts such as conveyor belts; rolls such as rubber cover rolls and printing rolls; gaskets; seals such as oil seals; packings; hoses such as oil-resistant hoses, etc.), building members (window frame rubber, vibration damping materials, carpet bagging materials, etc.), transportation members (automotive members, tires, power transmission belts, etc.), and electric and electronic equipment members (wire coatings, etc.).
Claims
1. A composite material comprising a fibrous filler (A) derived from a plant and an organic material (B) and having a bulk density of 0.1 to 0.5 g / cm 3 A granule comprising: The average fiber diameter of the fibrous filler (A) is 0.5 to 100 μm, The organic material (B) is a solid at room temperature and normal pressure, and The organic material (B) has a molecular weight of 100 to 1,000.
2. 2. The granule according to claim 1, wherein the ratio of the organic material (B) is 1 to 70 parts by mass per 100 parts by mass of the fibrous filler (A).
3. 3. The granules according to claim 1 or 2, which are used for kneading with resin or rubber.
4. 3. The granule according to claim 1, wherein the organic material (B) is a non-fibrous organic material having a melting point of 100° C. or higher.
5. 3. The granule according to claim 1, wherein the organic material (B) is a compound having a hydrophobic skeleton and a polar group.
6. The granule according to claim 5, wherein the hydrophobic skeleton is a polycyclic aromatic ring.
7. The granule according to claim 1 or 2, wherein the organic material (B) is a compound represented by the following formula (1): 【Chemistry 1】 (Wherein, ring Z is an arene ring, R 1 and R 2 is a substituent, X 1 represents a heteroatom-containing functional group, k represents an integer of 0 to 4, n represents an integer of 1 or more, and p represents an integer of 0 or more.
8. In the formula (1), X 1 is the group -(OA) m1 The granule according to claim 7, wherein A is an alkylene group and m1 is an integer of 0 or more.
9. 3. The granule according to claim 1, wherein the fibrous filler (A) is a cellulose fiber.
10. 3. The method for producing a granule according to claim 1, comprising: a mixing step of mixing a precursor of the plant-derived fibrous filler (A), a precursor of the organic material (B), and water to obtain a mixture; and a granulation step of granulating the obtained mixture to obtain a granule.
11. The method according to claim 10, wherein the mixture is extrusion-granulated in the granulation step.
12. A resin composition comprising the granules according to claim 1 or 2 and a resin.
13. The resin composition according to claim 12, wherein the resin is a thermoplastic resin.
14. A method for producing a resin composition, comprising a resin kneading step of kneading the granules according to claim 1 or 2 with a resin.
15. 13. A molded article of the resin composition according to claim 12, which is a part or material selected from the group consisting of automobile parts, electric and electronic parts, building materials, civil engineering materials, agricultural materials, packaging materials, living materials, and optical components.
16. A rubber composition comprising the granules according to claim 1 or 2 and a rubber.
17. A method for producing a rubber composition, comprising a rubber kneading step of kneading the granules according to claim 1 or 2 with rubber.
18. 17. A molded article made of the vulcanizate of the rubber composition according to claim 16, which is a belt, a roll, a gasket, an oil seal, a packing, a hose, a window frame rubber, a vibration damping material, a carpet bagging material, an automotive part, a tire or an electric wire coating.
Citation Information
Patent Citations
Fiber material to be blended in resin and resin composite used thereof
JP1993269736A
Thermoplastic resin composition and its molded article, and method for producing the same
JP2020041084A
Rubber-like composition and method for producing the same
JP2021011559A
Resin composition and conductivity improvement method
JP2022057221A
Dried product and method for producing the same, and method for producing resin composition
JP2022169489A